Systems and methods for mitigating heat transfer in battery-based energy storage systems

CN117157806BActive Publication Date: 2026-10-23ASPEN AEROGELS INC
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202280022052.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-28
Filing Date
2022-07-01
Publication Date
2026-10-23
Estimated Expiration
2042-07-01

AI Technical Summary

Benefits of technology

[0048]与现有的热失控缓解策略相比,本文中所述的方法和系统可提供一个或多个优点。本文中所述的多层材料可最大限度地减少或消除单元热传播,而不会显著影响电池模块或电池组的能量密度和组装成本。本公开的系统和方法的一些实施方案可提供良好的压缩性、压缩弹性及顺应性的属性,以适应在单元寿命期间持续的单元膨胀,同时在正常操作状况下以及在热失控状况下具有良好的热属性。本文中所述的方法和系统的特定实施方案耐用且易于处理,具有良好的抗热传播和火灾传播能力,同时最大限度地减小所用材料的厚度和重量,而且具有良好的压缩性、压缩弹性和/或顺应性的属性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0004451625990000011
    Figure HDA0004451625990000011
  • Figure HDA0004451625990000021
    Figure HDA0004451625990000021
Patent Text Reader

Abstract

The present disclosure relates to methods and systems to manage thermal runaway issues in energy storage systems. Exemplary embodiments include methods and systems having a compressible thermal barrier. The compressible thermal barrier is sized (e.g., thickness, volume, etc.) to prevent thermal propagation between adjacent cells, modules, and / or packs when a portion of an energy source experiences a thermal event. The methods and systems mitigate thermal propagation such that cells adjacent to a damaged cell (e.g., an actively burning cell) do not experience thermal runaway as it is shielded from heat dissipation and does not exceed a critical temperature. The present disclosure further relates to a battery module or battery pack having one or more battery cells and the compressible thermal barrier disposed between adjacent cells.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications This application claims priority and benefit to U.S. Provisional Patent Application No. 63 / 218,205, filed July 2, 2021, entitled “Materials, Systems, and Methods for Mitigation of Electrical Energy Storage Thermal Events”; U.S. Provisional Patent Application No. 63 / 324,060, filed March 26, 2022, entitled “Systems and Methods for Mitigating Thermal Propagation in Battery-Based Energy Storage Systems”; and U.S. Provisional Patent Application No. 63 / 324,522, filed March 28, 2022, entitled “Systems and Methods for Mitigating Thermal Propagation in Battery-Based Energy Storage Systems”, all of which are incorporated herein by reference in their entirety. Technical Field

[0002] This disclosure generally relates to systems and methods for mitigating thermal events (e.g., thermal runaway) in energy storage systems. In particular, this disclosure provides systems, methods, and techniques for preventing heat propagation in adjacent cells, modules, or groups after a thermal event (e.g., thermal runaway) has occurred in a portion of a battery-based energy storage system. This disclosure further relates to battery modules or battery packs having one or more battery cells, including an amount (e.g., thickness, volume, etc.) of insulating material to mitigate heat propagation according to the present technology, and systems including such battery modules or battery packs. Background Technology

[0003] Rechargeable batteries (such as lithium-ion batteries) are widely used in electric drive and energy storage systems. Compared to conventional batteries, lithium-ion batteries (LIBs) are widely used to power portable electronic devices such as mobile phones, tablets, laptops, power tools, and other high-current devices such as electric vehicles due to their high operating voltage, low memory effect, and high energy density. However, safety is a concern because LIBs are prone to catastrophic failure under “abuse conditions” (e.g., when rechargeable batteries are overcharged (charged beyond their design voltage), over-discharged, operated under or exposed to high temperatures and pressures). Therefore, narrow operating temperature ranges and charge / discharge rates limit the use of LIBs, as they may fail due to rapid self-heating or thermal runaway events when subjected to conditions outside their design window.

[0004] like Figure 1 As shown, the electrochemical unit of LIB mainly consists of a positive electrode, a negative electrode, an electrolyte capable of conducting lithium ions, a separator membrane separating the positive and negative electrodes, and a current collector. LiCoO2, LiFePO4, LiMn2O4, Li2TiO3, LiNi 0.8 Co 0.15 Al 0.05 O2(NCA) and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NMC) is one of the six cathode materials widely used in lithium-ion batteries. These six batteries account for a large market share in today's battery market. The electrolyte consists of lithium salts dissolved in specific solvents, primarily ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and propylene carbonate (PC). These lithium salts are typically selected from LiClO4, LiPF6, LiBF4, and LiBOB. The separator material is usually a polyolefin-based resin. In commercial lithium-ion batteries, polypropylene (PP) and polyethylene (PE) microporous membranes are commonly used as separators. Aluminum foil is typically used as the current collector for the positive electrode, while copper foil is used for the negative electrode. Carbon-based materials (including hard carbon, carbon nanotubes, and graphene) are currently the primary choice for most negative electrodes in commercial lithium-ion batteries; other novel negative electrode materials (such as titanium-based oxides, alloy / dealloy materials, and conversion materials) have also been studied and have shown good thermal and electrochemical performance.

[0005] LIB operation under normal conditions Under normal operation, lithium ions diffuse from one electrode and migrate through the electrolyte and separator to the other electrode.

[0006] Charging the LIB causes lithium ions in the electrolyte solution to migrate from the cathode through the separator and self-insert into the anode. Figure 2 Electrons that balance the charge also move to the anode, but pass through the external circuitry in the charger. During discharge, the reverse process occurs, and electrons flow through the powered device. Figure 2 During this process, heat is generated within the cell through three main mechanisms. The first is reversible heat, caused by entropy changes associated with redox reactions occurring during lithiation (discharging) and delithiation (charging). Reversible heat is also known as entropy heat. The second mechanism is irreversible heat associated with electrode polarization caused by overpotentials within the cell. Finally, there is irreversible heat associated with ohmic losses, known as Joule heating. Joule heating is attributed to the movement of lithium ions and electrons within the cell. Under normal conditions, self-generated heat is extremely low, usually negligible, and can be easily dissipated through good battery design or a battery thermal management system. However, under abuse conditions, several side reactions can occur, leading to thermal runaway. Understanding the causes of thermal runaway can guide the design of functional materials to improve the safety and reliability of lithium-ion batteries (LIBs).

[0007] Overview of thermal runaway and thermal runaway propagation Thermal runaway can occur when the internal reaction rate increases to the point that the heat generated exceeds the recoverable heat, leading to a further increase in both the reaction rate and heat generation. During thermal runaway, the high temperature triggers a series of exothermic reactions within the battery, causing the battery temperature to rise rapidly. In many cases, when thermal runaway occurs in a battery cell, the resulting heat rapidly heats cells immediately adjacent to the one experiencing runaway. Each cell added to the runaway reaction contains additional energy to continue the reaction, causing thermal runaway to propagate within the battery pack. Figure 3 This can ultimately lead to fire or explosion disasters. Rapid heat dissipation and effectively blocking heat transfer paths can be effective countermeasures to reduce the harm caused by the spread of thermal runaway.

[0008] Causes of thermal runaway - abuse Thermal runaway can be triggered by various forms of abuse, including mechanical abuse, electrical abuse, and thermal abuse. Figure 3 Each form of abuse can induce an internal short circuit (ISC) in the battery, leading to increased temperature. Abuse conditions can begin externally or internally. For example, service-induced stress, aging, design errors (such as configuration parameters like cell spacing), cell interconnection patterns, cell form factor, manufacturing, operation, and maintenance are internal factors that can cause various forms of abuse. External factors include damage or injury to the LIB, such as from drops or cell penetration.

[0009] mechanical abuse Mechanical abuse is primarily caused by mechanical forces and typically occurs due to external factors such as severe car crashes, including collisions, crushes, penetrations, and bends. When a battery or battery pack is subjected to impact or a collision, potential damage to the battery's internal structure can occur, including rupture of the separator and leakage of flammable electrolytes, triggering an internal short circuit (ISC) and subsequently leading to thermal runaway. Destructive deformation and displacement caused by applied forces are two common characteristics of mechanical abuse. Battery packs are highly likely to deform during a car crash. The layout of the battery pack in an electric vehicle affects its crash response. Deformation of the battery pack can lead to dangerous consequences: the separator may be torn, resulting in an internal short circuit (ISC); flammable electrolytes may leak, potentially causing a fire. Penetration is another common phenomenon that can occur during a vehicle crash. Compared to crush conditions, when penetration begins, it can trigger a violent ISC instantaneously. Mechanical damage occurs simultaneously with electrical short circuits, and penetration abuse can be more severe than simple mechanical or electrical abuse.

[0010] electrical abuse Electrical abuse mainly includes internal or external short circuits in the LIB, overcharging, and over-discharging.

[0011] Internal short circuits occur in over 90% of abuse cases. Broadly speaking, an internal short circuit occurs when the cathode and anode come into contact due to the failure of the battery separator. Internal short circuits can be caused by (1) mechanical abuse, when the separator ruptures due to penetration or compression; and (2) electrical abuse, when the separator is punctured by dendrite growth. Figure 4 ( ); and (3) heat abuse, when the separator breaks down at high temperature.

[0012] An external short circuit occurs when electrodes with a voltage difference are connected through a conductor. External short circuits in battery packs can be caused by deformation during a car crash, water immersion, conductor contamination, or electric shock during maintenance. Typically, the heat released from an external short circuit does not heat the cells compared to penetration. An external short circuit can lead to high current and heat generation in the battery, primarily due to ohmic heat. Cell damage begins when the temperature starts to exceed approximately 70°C. This can trigger venting and electrolyte leakage.

[0013] Overcharging can be defined as charging a battery beyond its design voltage. Overcharging can be triggered by high specific current density, aggressive charging curves, etc., and can lead to a series of problems including: lithium metal deposition on the anode, which seriously affects the battery's electrochemical performance and safety; decomposition of the cathode material, releasing oxygen; and decomposition of organic electrolytes, releasing heat and gaseous products (H2, hydrocarbons, CO, etc.). The overcharging process can be divided into three stages. In the first stage, (1) the voltage and temperature are unaffected and remain essentially unchanged. In the second stage, (2) lithium dendrite deposition occurs on the voltage plateau. Then in the third stage, (3) with the generation of heat and gas, the voltage drops sharply, causing thermal runaway of the battery.

[0014] Over-discharge is another possible form of electrical abuse. Voltage inconsistencies between cells within a battery pack are typically unavoidable. Therefore, if the battery management system cannot monitor the voltage of any individual cell, the cell with the lowest voltage will be over-discharged. The mechanism of over-discharge abuse differs from others, and its potential hazards may be underestimated. During over-discharge, the cell with the lowest voltage in the battery pack can be forced to discharge by other cells connected in series. During forced discharge, the electrodes reverse and the cell's voltage becomes negative, leading to abnormal heat generation in the over-discharged cell.

[0015] Heat abuse Thermal abuse is typically triggered by overheating. Overheating in lithium-ion batteries can be caused by mechanical abuse, electrical abuse, and contact loss in connectors. Typically, LIBs are stable at normal operating temperatures; however, above certain temperatures, LIB stability becomes unpredictable, and at high temperatures, chemical reactions within the battery case produce gases, leading to increased internal pressure. These gases can further react with the cathode, releasing more heat and generating heat within or near the battery, which can ignite the electrolyte in the presence of oxygen. When the electrolyte burns, oxygen is produced, further promoting combustion. At some point, the pressure buildup within the battery case can cause it to rupture. The escaped gases may ignite and burn.

[0016] Thermal runaway caused by mechanical, electrical, and thermal abuse conditions can induce sustained heat generation, thus raising the internal temperature of the battery. As the temperature increases, a series of chain reactions may occur at different stages. Thermal runaway follows a chain reaction mechanism, such as physical and / or chemical processes, during which the decomposition reactions of battery component materials occur sequentially. Figure 3 ).

[0017] Overview of chain reactions during thermal runaway Understanding the evolution of these physical and / or chemical processes helps in developing mitigation strategies for thermal runaway in LIBs. LIBs can have different thermal runaway triggers under different temperature states or modes. Figure 5 The states include: State I: low temperature (<0℃), State II: normal temperature (0~90℃), and State III: high temperature (>90℃).

[0018] In State I, LIBs cannot operate effectively because the low temperature reduces the rate of electrochemical reactions. At lower temperatures, battery performance deteriorates sharply due to the reduced activity of electrode materials and the decreased diffusion rate of lithium ions in the electrolyte. The consequences of the slowed chemical reactions at low temperatures include undesirable lithium deposition, plating, and dendrite growth. Dendrites are tree-like structures that can form on the lithium plating in the battery. They can rapidly penetrate the battery's separator (the porous plastic membrane located between the anode and cathode of the battery). Figure 4 Lithium deposition and dendrite growth within the cell are considered major contributing factors to thermal runaway at low temperatures. Unbound by theoretical constraints, it is believed that undesirable lithium deposition and dendrite growth can induce intercellular charge (ISC) in the battery, leading to thermal runaway.

[0019] In State II (normal temperature operation), heat generation is minimal compared to that generated during thermal runaway. Heat generation during this operating state is primarily caused by lithium-ion diffusion in the solid-liquid phase, electrochemical reactions at the solid-liquid interface, and side reactions. This heat generation can cause temperature rise and internal temperature differences within the battery, which can affect the lifespan and safety of the lithium-ion battery. During State II, initial overheating can occur due to at least one of the aforementioned internal or external triggers, such as overcharging, exposure to excessively high temperatures, external short circuits due to wiring faults, or internal short circuits due to cell defects. When initial overheating begins, battery operation changes from a normal state to an abnormal state as the temperature rises towards 90°C. When the temperature exceeds 40°C, the lifespan of the lithium-ion battery may be shortened due to accelerated side reactions, and when the temperature approaches 90°C or higher, it can trigger the decomposition of the solid electrolyte interphase (SEI) film, which is defined as the onset of thermal runaway. During the first few charging cycles, an SEI is formed on the anode of the lithium-ion battery. The SEI provides a passivation layer on the anode surface, which inhibits further electrolyte decomposition and provides the long calendar lifetime required for many applications. Initial decomposition of the SEI is considered the first side reaction to occur during a fully thermal runaway process. Initial decomposition of the SEI occurs between 80 and 120 °C, peaking at approximately 100 °C. The onset temperature can be below 80 °C; as reported by Wang et al. (Thermochim. Acta 437 (2005) 12-16), SEI decomposition may begin at temperatures as low as 57 °C.

[0020] SEI decomposition When stage III begins, the internal temperature rises rapidly, leading to the decomposition of the SEI film. The SEI layer is mainly composed of stable (e.g., LiF and Li₂CO₃) and metastable (e.g., polymers, ROCO₂Li, (CH₂OCO₂Li)₂, and ROLi) components. However, the metastable component can decompose exothermically at approximately >90°C, releasing flammable gases and oxygen. The decomposition of the SEI film is considered the beginning of thermal runaway, which subsequently triggers a series of exothermic reactions.

[0021] As the SEI decomposes, the temperature rises, and the lithium metal or intercalated lithium in the anode reacts with the organic solvent in the electrolyte, releasing flammable hydrocarbon gases (ethane, methane, and others). This is an exothermic reaction, driving the temperature to rise further.

[0022] Decomposition of the separator When T > ~130℃, the polyethylene (PE) / polypropylene (PP) separator begins to melt, which further exacerbates the situation and causes a short circuit between the cathode and anode. Although the melting of the PE / PP separator is a thermal adsorption process, the inter-phase flow (ISC) caused by the separator melting will further worsen the thermal runaway process.

[0023] Gas emissions and electrolyte decomposition When T > ~180℃, the heat generated by the ISC causes the lithium metal oxide cathode material to decompose, leading to the release of oxygen. The decomposition of the cathode is also highly exothermic, further increasing temperature and pressure, and thus accelerating the reaction. Subsequently, the heat buildup and gas release (oxygen and flammable gases) will induce combustion and explosion of the lithium-ion battery.

[0024] During thermal runaway, only 2% of the heat is generated by ISC (Inductively Coupled Discharge), while chemical reactions account for 98%, including the decomposition of the SEI layer and the electrolyte. The largest proportion of heat generation is caused by the rapid redox reaction between the cathode and anode, approximately 48%, while the heat generation from other chemical reactions in the anode, cathode, and electrolyte is much smaller. The smallest heat generation is the decomposition of the SEI film.

[0025] The need for strategies to mitigate thermal runaway Based on the understanding of the mechanisms leading to battery thermal runaway, numerous approaches are being investigated to mitigate safety hazards through the rational design of battery modules. To prevent such cascading thermal runaway events, battery-in-the-brick (LIB) systems are typically designed to maintain sufficiently low energy storage, or to use adequate insulation between cells within the module or pack to protect these cells from potential thermal events in adjacent cells, or a combination of both. The former severely limits the energy that can be stored in such devices. The latter restricts the spacing between cells, thus limiting the effective energy density. Effective insulation and heat dissipation strategies are needed to mitigate the potential for thermal runaway in LIBs.

[0026] Current heat dissipation methods used in LIB Currently, many different methods are used to maximize energy density while preventing cascading thermal runaway. One method is to incorporate sufficient insulation between cells or clusters of cells. This method is generally considered for safety reasons; however, in this method, the thermal control capability of the insulating material and the required insulation volume determine the upper limit of the achievable energy density. Another method is to use phase change materials. These materials undergo an endothermic phase change when a certain high temperature is reached. This endothermic phase change absorbs part of the heat generated, thereby cooling a localized area. Typically, for electrical storage devices, these phase change materials rely on hydrocarbon materials, such as waxes and fatty acids. These systems are effective in cooling, but they are themselves flammable, so they are not conducive to preventing thermal runaway should a fire occur within the storage device. Combining expandable materials is another strategy to prevent cascading thermal runaway. These materials expand above a specified temperature to produce carbon, which is designed to be lightweight and provide thermal insulation when needed. These materials can effectively provide insulation benefits, but the expansion of the materials must be considered in the design of the storage device.

[0027] The need for novel thermal barriers to meet the mechanical requirements of LIB systems. Swelling of the anode and cathode during charging and discharging can lead to changes in cell size (expansion). For example, silicon typically exhibits a volume change of up to 300% during insertion, while graphite shows a volume expansion of approximately 10%. This change has both reversible and irreversible components, the levels of which depend on precise cell chemistry. Reversible changes in cell thickness depend solely on the cell's state of charge (SOC) and can result in thickness increases exceeding 2%. Irreversible cell expansion is associated with increased pressure within the cell and is caused by the formation of the SEI (Sediment-Insulated Layer). The largest component of this change occurs during the first charge cycle, when the SEI initially forms, but the expansion continues throughout the cell's lifetime.

[0028] While extensive research has been conducted to invent novel materials with favorable thermal properties to prevent thermal runaway, the mechanical properties of these materials, despite their importance, have not received sufficient attention. For example, there is a need for effective thermal barriers between cells within a battery module or pack, providing resistance to compressive deformation to accommodate continuous cell expansion throughout the cell's lifespan. Furthermore, during the initial assembly of a battery module, relatively low loads of 1 MPa or less are typically applied to the materials between cells. As the cells within a battery module or pack expand or grow during charge / discharge cycles, loads up to approximately 5 MPa may be applied to the materials between cells. Therefore, the compressibility, compressive elasticity, and compliance of materials (e.g., thermal barriers between cells) are important properties.

[0029] Therefore, a novel thermal barrier is needed to meet the mechanical requirements of LIB systems in order to provide effective insulation under thermal runaway conditions and effective heat dissipation under normal conditions. Summary of the Invention

[0030] The purpose of this disclosure is to eliminate or reduce at least one drawback of the prior methods and systems described above, in order to prevent or mitigate heat propagation in rechargeable battery systems (e.g., lithium-ion batteries). This disclosure provides methods and systems including a compressible thermal barrier. The compressible thermal barrier of this disclosure is sized to prevent heat propagation between adjacent units, modules, and / or groups when portions of an energy source experience thermal events.

[0031] In the context of this disclosure, mitigation of heat propagation means that the cell adjacent to the damaged cell (i.e., the cell that has experienced a thermal event above the critical temperature) does not experience thermal runaway. In other words, the cell adjacent to the damaged cell is shielded from the heat dissipated by the damaged cell. Due to such shielding or barrier layers, the temperature within the adjacent cell does not exceed the critical temperature, and therefore the cell adjacent to the damaged cell is not forced into thermal runaway.

[0032] In particular, the purpose of this disclosure is to provide methods and systems for mitigating heat propagation by using insulating materials of predetermined dimensions. These methods and systems are based on an understanding of the areal energy density of individual cells (i.e., the energy stored in a cell over an area where energy can be transferred to adjacent cells). The predetermined dimensions (e.g., thickness) are tailored to meet the areal energy density requirements of the cells. In some embodiments, the predetermined thickness prevents heat propagation from a thermally damaged cell to any adjacent cell. In a particular embodiment, the predetermined thickness is selected such that its compressible thickness (i.e., compressed between two adjacent cells during operation) prevents heat propagation from the damaged cell to the adjacent cell. Typically, the compressible thermal barrier provides protection against this heat propagation for a longer period of time, such as the entire duration of the damage to the damaged cell (i.e., the entire combustion event of the damaged cell). In a particular embodiment, the thickness of the compressible thermal barrier is selected to provide protection for a specific period of time; for example, 25 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 5 hours, or 24 hours. In certain embodiments, the thickness of the compressible thermal barrier disposed between adjacent units / modules / groups, etc., in its uncompressed state has a predetermined dimension (e.g., thickness) in the range of 1.5 mm to about 7 mm. In some embodiments, the thickness of the compressible thermal barrier disposed between adjacent units / modules / groups, etc., in its uncompressed state has a predetermined dimension (e.g., thickness) in the range of 2 mm to about 6 mm. Upon compression, the thickness of the compressible thermal barrier decreases compared to its uncompressed state. Typical compressed thicknesses range from about 0.8 mm to 6 mm. In some embodiments, the compressed thickness is about 1.0 mm; about 1.25 mm; about 1.5 mm; about 1.75 mm; or about 2.0 mm.

[0033] Another object of this disclosure is to provide a battery module or battery pack having a system and method according to this disclosure, which protects the battery pack from thermal damage due to thermal runaway of a cell and ensures the safe design of the battery pack.

[0034] In one general aspect, this disclosure aims to provide a battery module and a battery pack that simultaneously improve the heat dissipation performance and thermal runaway protection performance of a power battery. Please refer to... Figure 6In electric drive and energy storage systems, several cells 100 are typically packaged together in a pre-selected configuration (e.g., in parallel, series, or combined) to form a battery module 200. Accordingly, several such battery modules can be combined or connected to form various battery packs 300 known in the art. During operation and discharge, such cells, battery modules, or battery packs typically generate or produce a significant amount of heat, which can severely and adversely affect the resulting performance. Therefore, to maintain the desired or optimal performance of such cells or the resulting battery modules or battery packs, it is generally important to keep the temperature of such cells, battery modules, or battery packs within a narrow, specified range. The purpose of this disclosure is to maintain the temperature of such cells, battery modules, or battery packs within an optimal range.

[0035] In addition to maintaining the cell's temperature within a specified range, the aim is also to maintain the cell's structural integrity. The materials within the cell must possess both compliance and elasticity to accommodate volume changes during battery operation. In some embodiments, the method and system include flame-retardant or fire-resistant materials incorporated therein to maintain structural integrity after or during thermal events.

[0036] In embodiments of the current method and system, the compressible thermal barrier is provided as a single layer of insulating material. In some embodiments, the insulating material is in the form of an aerogel. In certain embodiments, the aerogel may be formed from a composite material. In some embodiments, the aerogel may include additives. Typically, the insulating material is compressible.

[0037] While some embodiments of this disclosure feature a single-layer thermal barrier disposed between adjacent cells, this disclosure is not limited to a single-layer material. For example, some embodiments feature a multi-layer material as a thermal barrier in an energy storage system to address heat propagation problems in battery modules or battery packs and to stop or mitigate heat propagation in the event of thermal runaway in one cell. The unique configuration of the multi-layer material of this disclosure can help address heat propagation problems between cells. Generally, the multi-layer thermal barrier comprises one or more layers of insulating material. The size or number of these insulating layers is customized according to this disclosure to mitigate heat propagation.

[0038] On one hand, this document provides a multilayer material for use as a thermal barrier in an energy storage system, comprising: a core portion, including a layered assembly comprising at least one insulating layer and at least one thermally capacitive layer alternately stacked along a direction perpendicular to its maximum surface; and an outer portion disposed outside the core portion, the outer portion comprising at least one sacrificial material layer and at least one encapsulating material layer, the at least one sacrificial material layer comprising a compressible pad, and the at least one encapsulating material layer selected from polymers, elastomers, or combinations thereof. Without being limited to theory, it is considered that when a predetermined size of a thermal barrier comprising a multilayer material is selected, the size selected to prevent heat propagation will be applied to the thickness of the one or more insulating layers of the multilayer material.

[0039] In one or more embodiments, the multilayer material according to any of the foregoing aspects has an average thickness in the uncompressed state ranging from about 2 mm to about 10 mm. In some embodiments, in the uncompressed state, the thickness of the insulating layer within the multilayer material ranges from about 1 mm to about 7 mm. In a particular embodiment, the insulating layer of the multilayer material has a predetermined dimension (e.g., thickness) in the uncompressed state ranging from 1.5 mm to about 5 mm. In the compressed state, the insulating layer may have a thickness between about 0.75 mm and about 2.5 mm, for example, about 1.25 mm or about 1.5 mm.

[0040] Implementations of the above aspects, methods, and systems may include one or more of the following features. In some embodiments, the one or more insulating layers (if a multilayer material is used in the thermal barrier) or a single-layer thermal barrier comprises an aerogel and may further comprise a reinforcing material. In some embodiments, the reinforcing material is selected from fibers of organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. In some embodiments, the fibers are in the form of discrete fibers, woven materials, dry-laid nonwoven materials, wet-laid nonwoven materials, needle-punched nonwoven fabrics, wadding, nets, mats, felts, and / or combinations thereof. In some embodiments, the inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof. In one or more embodiments, the aerogel comprises a silica-based aerogel. In one or more embodiments, the aerogel comprises one or more additives at a level of at least about 5 to 40 weight percent of the aerogel, preferably at a level of at least about 5 to 20 weight percent of the aerogel, and more preferably at a level of at least about 10 to 20 weight percent of the aerogel. In some embodiments, the one or more additives include fire-retardant additives. In some embodiments, the one or more additives include a light-blocking agent selected from B4C, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, TiC, WC, carbon black, titanium dioxide, ferrotitanium dioxide, zirconium silicate, zirconium oxide, iron oxide (I), iron oxide (III), manganese dioxide, ferrotitanium dioxide (ilmenite), chromium oxide, or mixtures thereof. In some embodiments, the one or more additives include a light-blocking agent comprising silicon carbide. In some embodiments, the one or more additives include a combination of fire-retardant additives and light-blocking agents. In one or more embodiments, the aerogel has a density in the range of about 0.25 g / cc to about 1.0 g / cc. In one or more embodiments, the aerogel is in the form of monoliths, microbeads, granules, small particles, powders, films, flakes, or combinations thereof.

[0041] In another embodiment, a multilayer material used as a thermal barrier in an energy storage system includes: a core portion comprising an insulating layer having a thermal conductivity of less than about 50 mW / mK at 25°C and less than about 60 mW / mK in a thickness dimension extending through the insulating layer; and an outer portion disposed outside the core portion, the outer portion comprising a thermally conductive layer having a thermal conductivity of at least about 200 mW / mK in an in-plane dimension along the thermally conductive layer.

[0042] In one embodiment, the thermally conductive layer is divided into a first thermally conductive layer and a second thermally conductive layer located on opposite sides of the thermally conductive layer, wherein the first thermally conductive layer and the second thermally conductive layer are in contact with the insulating layer. In a specific embodiment, the thermally conductive layer is substantially L-shaped, such that the vertical portion of the L-shaped thermally conductive layer is spaced apart from the insulating layer. The horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer. One or more of an encapsulating material layer, a sacrificial material layer, and a thermal capacitance layer may be disposed between the vertical portion of the L-shaped thermally conductive layer and the insulating layer.

[0043] In one embodiment, a battery module includes: a first battery cell having a first surface; a second battery cell having a second surface opposite to the first surface; and a multilayer material having a core portion including an insulating layer and an outer portion disposed outside the core portion, the outer portion including a thermally conductive layer. The battery module further includes a heat exchange system in contact with the first battery cell, the second battery cell, and the thermally conductive layer of the multilayer material. In one embodiment, the multilayer material covers at least about 80% of the surface area of ​​the opposing first and second surfaces. In one embodiment, the insulating layer of the multilayer material extends into the heat exchange system.

[0044] The thermally conductive layer of the multilayer material is in thermal communication with the heat exchange system and the battery cell. This thermal communication between the multilayer material and the battery cell can be achieved by providing a thermally conductive material in contact with the surface of the battery cell. This configuration allows heat generated by the battery cell to be drawn into the heat exchange system through the thermally conductive layer.

[0045] By incorporating suitable multilayer materials between battery cells, heat propagation from battery cells undergoing thermal runaway can be suppressed or minimized. In one embodiment, the multilayer material has a thermal resistivity of at least 0.01. This thermal resistivity is the ratio of the thermal resistance of the multilayer material to the areal energy density of the battery cells in the battery module. The areal energy density of the battery cell array is the ratio of the total energy density of all cells in the array to the outer surface area of ​​the array. The multilayer material may also have a thickness coefficient of at least about 0.3. This thickness coefficient is the ratio of the thickness of the multilayer material to the areal energy density of the battery cells.

[0046] In one embodiment, a method of designing an energy storage system includes: assembling one or more battery cells to form an array; calculating the area energy density of the array; selecting the thermal resistance and compressibility thickness of a multilayer material based on the area energy density of the array, such that the energy storage system has a thermal resistance coefficient of at least about 0.01 and a thickness coefficient of at least about 0.3; and disposing the multilayer material in and / or around the array. In one embodiment, the cell area energy density of the array is known. In this embodiment, selecting the compressibility thickness of the multilayer material capable of suppressing runaway propagation includes: calculating the thermal resistance coefficient of the multilayer material; reading the minimum compressibility thickness of the multilayer material from a thermal propagation diagram; and selecting a compressibility thickness greater than the minimum compressibility thickness. Similarly, selecting the thermal resistance and the compressibility thickness can also be performed by the following steps: calculating the thickness coefficient of the multilayer material that can be disposed between the battery cells of the array; reading the minimum thermal resistance of the multilayer material from a thermal propagation diagram; and selecting a thermal resistance greater than the minimum thermal resistance for the multilayer material.

[0047] On the other hand, this document provides an apparatus or vehicle including a battery module or battery pack according to any of the foregoing aspects. In some embodiments, the apparatus is a laptop computer, PDA, mobile phone, tag scanner, audio device, video device, display panel, camera, digital camera, desktop computer, military portable computer, military telephone, laser rangefinder, digital communication device, intelligence gathering sensor, electronic integrated clothing, night vision device, power tool, calculator, radio, remote control device, GPS device, handheld and portable television, car starter, flashlight, acoustic device, portable heating device, portable vacuum cleaner, or portable medical tool. In some embodiments, the vehicle is an electric vehicle.

[0048] Compared to existing thermal runaway mitigation strategies, the methods and systems described herein offer one or more advantages. The multilayer materials described herein minimize or eliminate cell heat propagation without significantly impacting the energy density and assembly cost of the battery module or pack. Some embodiments of the systems and methods disclosed herein offer good compressibility, compressive resilience, and compliance properties to accommodate continuous cell expansion throughout the cell's lifespan, while maintaining good thermal properties under normal operating conditions and thermal runaway conditions. Certain embodiments of the methods and systems described herein are durable and easy to handle, offering good resistance to heat and fire propagation while minimizing the thickness and weight of the materials used, and possessing good compressibility, compressive resilience, and / or compliance properties. Attached Figure Description

[0049] After summarizing this disclosure, reference will now be made to the accompanying drawings, which are not necessarily drawn to scale, and in which: Figure 1A schematic diagram of the electrochemical unit of a lithium-ion battery is shown. Figure 2 This diagram illustrates the charging-discharging process in a lithium-ion battery.

[0050] Figure 3 The diagram illustrates the thermal runaway abuse condition and thermal runaway propagation process within the battery module.

[0051] Figure 4 A schematic diagram showing dendrite growth on a lithium coating in a battery.

[0052] Figure 5 The diagram illustrates the three stages that lead to thermal runaway.

[0053] Figure 6 The diagram illustrates battery cells, battery modules, and battery packs.

[0054] Figure 7 Showing a front view of a test apparatus for testing the heat transfer capability of a thermal barrier according to the embodiment disclosed herein.

[0055] Figure 8 Display utilization Figure 7 The diagram shows a temperature comparison between the triggering unit (i.e., the unit that experienced thermal runaway) and its adjacent units in the device test shown.

[0056] Figure 9A and Figure 9B show Figure 7 The apparatus shown in the diagram was used to test several cells with different thermal barrier thicknesses between the triggering cell and adjacent cells.

[0057] Figure 9C Display utilization Figure 7 The parameter table shows several different square and bag-shaped units tested by the apparatus shown.

[0058] Figure 10 The illustration shows multi-layered materials based on a specific embodiment disclosed herein.

[0059] Figure 11 The illustration shows multi-layered materials based on a specific embodiment disclosed herein.

[0060] Figure 12A -E schematically illustrates multi-layered materials according to a specific embodiment disclosed herein.

[0061] Figure 13 The diagram illustrates a multilayer material with a core insulating layer.

[0062] Figure 14 The flowchart illustrates a method for manufacturing a battery cell module.

[0063] Figure 15 The illustration shows a battery module or battery pack with multiple battery cells protected by multiple layers of materials. Detailed Implementation

[0064] In the following detailed description of preferred embodiments, reference is made to the accompanying drawings, which form part of these embodiments and illustrate specific embodiments by way of example, through which this disclosure may be implemented. It should be understood that other embodiments may be used and structural changes may be made without departing from the scope of this disclosure.

[0065] Generally, this technology relates to systems and methods for mitigating thermal events (e.g., thermal runaway) in energy storage systems. In particular, this technology provides systems, methods, and techniques for preventing heat propagation in adjacent cells, modules, or groups after a thermal event (e.g., thermal runaway) has occurred in a portion of a battery-based energy storage system. This disclosure further relates to battery modules or battery packs having one or more battery cells, including an amount (e.g., thickness, volume, etc.) of insulating material to mitigate heat propagation according to this technology, and systems including such battery modules or battery packs.

[0066] The trigger unit (i.e., the thermally damaged unit) in the energy storage system of this technology is sandwiched between two adjacent units. The adjacent units are not yet affected by the heat released by the trigger unit. Insulating material is sandwiched between each adjacent unit and the trigger unit. During the use of the energy storage system, the insulating material is compressed and covers the inter-unit surfaces between the adjacent units and the trigger unit. Typically, the energy storage system is provided with a cooling plate that is in thermal contact with all units. The cooling plate appears at the bottom of the storage system. To prevent inter-unit heat transfer, for a trigger unit with an electrochemical capacity of E* and a total heat release potential of 5E*, four main energy flows are considered. First, (1) conduction from the trigger unit to the adjacent units must be addressed. Approximately 0.15E* through each surface of the trigger unit should be addressed. Second, (2) conduction into the cooling plate removes a portion of the heat released by the trigger unit. The heat absorbed by the cooling plate will depend on the type of cooling plate used - active cooling removes more heat. Third, (3) some heat will be released from the trigger unit as solids, liquids, and / or gases. This heat is discharged into the head space of the energy storage system. Finally, (4) once the trigger unit burns, the amount of heat released will depend on oxygen availability and chemical decomposition pathways. To address heat propagation and provide the longest possible protection to the adjacent unit from the heat release of the trigger unit, the management of the heat conduction of the trigger unit and the discharged gas and materials must be addressed. In addressing the conduction problem between the trigger unit and the adjacent unit, the insulation material according to this technology provides superior mechanical and thermal properties. In other words, the insulation material manages two key aspects at the interface between the units. First, the insulation material allows the unit to expand and breathe because it absorbs mechanical energy (high stress and large strain) with minimal fatigue or compressive deformation. Second, since it can withstand temperatures of 1000°C or higher (up to 1400°C) even when compressed, the insulation material allows for delaying or preventing heat propagation.

[0067] It is desirable that the thermal barrier between adjacent cells be compressible and capable of absorbing volume fluctuations during the operation of the energy storage system. The object of this invention is not only to provide a compressible thermal barrier, but also to provide a thermal barrier that mitigates heat propagation from a damaged cell (e.g., a combustion cell in thermal runaway) to an adjacent cell. To mitigate heat propagation, it is necessary to prevent the adjacent cell (i.e., not yet a damaged cell) from exceeding a critical temperature (at which thermal runaway predominates). To this end, this technique modifies the dimensions of its compressible thermal barrier based on the cell's area energy density. The cell area energy density, as used herein, is defined as the ratio of the total energy density of all cells in the array to the outer surface of the cell array divided by the area of ​​the heat transfer surface of that cell. Not limited to theory, it is believed that protection can be achieved by customizing the compressible thickness of the thermal barrier in conjunction with the area energy density of a specific cell. Furthermore, it is believed that the desired amount / thickness of the compressible thermal barrier (in the uncompressed state) can be determined using the linear relationship between the compressible thickness of the thermal barrier and the area energy density.

[0068] To determine the relationship between area energy density and thickness, a testing device was designed and manufactured. Figure 7 The test apparatus is shown in the image. It includes two clamping surfaces to compress the trigger unit (i.e., the unit that will be damaged during testing) together with an adjacent unit. A thermal barrier is positioned between the two units. Figure 7 This is an image before testing (i.e., in the uncompressed state). The thermal barrier shown, sandwiched between the trigger unit and the adjacent unit, has a thickness of 2.35 mm. Other thicknesses can also be used, including 2, 3, and 4 times the thickness of the 2.35 mm thermal barrier, and the thickness of the thermal barrier can be evaluated in different tests.

[0069] Figure 7 In the proposed implementation, each trigger unit and adjacent unit is a prismatic unit, each with a 62Ah storage capacity. To begin testing, the clamping surfaces are forced close together to provide pressure on the unit surfaces. Please refer to... Figure 8 In a 4.7 mm thick thermal barrier (i.e., Figure 7 In the test (shown as twice the thickness of 2.35 mm), a unit surface pressure of 560 kPa was generated. From Figure 8 As can be seen on the right, the surface pressure of this unit is relatively stable until the trigger unit begins to experience the first stage of a thermal event. When the voltage in the trigger unit decreases, the surface pressure initially increases until an extreme temperature change occurs within the trigger unit. This extreme temperature change is believed to correspond to a combustion event (i.e., flame generation and escape from the trigger unit). On the timeline, this combustion event is recorded at time zero, marking the beginning of the active thermal runaway of the trigger unit.

[0070] During the subsequent few minutes of testing, the trigger unit experienced thermal runaway. However, the 4.7 mm thick thermal barrier (measured in its uncompressed state) shielded the adjacent unit from heat dissipation, thus preventing the adjacent unit from exceeding the critical temperature (i.e., the temperature of the trigger unit at time 0 minutes).

[0071] By protecting the adjacent cell from the heat dissipation of the triggering unit, the adjacent cell remains below the critical temperature even when the triggering unit (immediately adjacent to the adjacent cell) is in thermal runaway. Therefore, the 4.7 mm thick uncompressible thermal barrier (formed from aerogel) mitigates or prevents heat propagation between the two square cells (each with a storage capacity of 62 Ah).

[0072] Figure 8 The multilayer materials used in the examples discussed include a thermally conductive layer, a heat-absorbing layer, a heat-resistant layer, and a heat-insulating layer. Each layer blocks or removes heat generated by adjacent battery cells. However, some layers play different roles at specific stages of the runaway process. In the first stage, the battery operates under standard operating conditions, and the outer thermally conductive layer removes heat from adjacent cells and directs it to the heat exchange element. In the second stage of the runaway process, the temperature of the battery cell begins to rise significantly (reaching above 90°C), causing the battery cell to break down. Some heat continues to be transported by the thermally conductive layer (e.g., to the heat exchange element). The additional heat generated by the battery cell is absorbed by the heat-absorbing layer (heat-capacity layer). As the runaway process continues, the sudden rise in temperature exceeds the capacity of the first two cooling systems (thermally conductive and heat-capacity layers). Heat then reaches the heat-resistant layer (sacrificial layer), which absorbs some of the heat generated by the runaway cell as the layers decompose. The final layer used to prevent heat from the runaway battery cell from reaching other cells is the insulating layer. After the first three layers, the heat has been sufficiently dissipated, thus preventing heat from reaching adjacent cells. For example... Figure 8 As shown, the temperature of the adjacent battery cells is maintained at 100°C or below through this multilayer material.

[0073] Please refer to Figure 9C ,use Figure 7 The test setup shown tests four test samples to generate results and performance plots. Test samples AAI T1 and AAI T3 have an uncompressed thickness of 2.35 mm; while test samples AAI T2 and AAI T4 have an uncompressed thickness of 4.70 mm (twice the thickness of T1 and T3). The cell-face pressure (CFP) applied or generated for test sample AAI T1 is 275 kPa, for AAI T2 it is 275 kPa, for AAI T3 it is 580 kPa, and for AAI T4 it is 560 kPa. The areal energy density (kAh / m²) of these samples is... 2Approximately 2 kAh / m 2 .

[0074] Figure 9C The display shows that when the compressive force (i.e., the unit surface pressure) is below 300 kPa (specifically 275 kPa), Figure 7 The 2.35 mm or 4.70 mm thermal barrier thickness shown is sufficient to mitigate / prevent heat propagation between the two cells. In fact, the delay or protection given to adjacent cells continues until the thermal event of the triggering cell ends (i.e., combustion ends after all heat has dissipated from the triggering cell). The thickness of the uncompressed thermal barrier was tested when the cell surface pressure increased by two times or more (i.e., 560 kPa or greater). For sample AAI T3 with a thickness of 2.35 mm, some mitigation of heat propagation to adjacent cells was provided (28-minute delay). By doubling the thickness of the thermal barrier to 4.70 mm (i.e., sample AAI T4), heat propagation to adjacent cells was prevented.

[0075] Performance graphs were generated by testing different thermal barrier thicknesses under varying compression conditions for different unit types and configurations. Figure 9A The dashed line in the performance graph on the right indicates the relationship between area energy density and the compressible thickness of the thermal barrier. Clearly, applying / generating greater pressure on the unit surface will lead to a reduction in the compressible thickness of the insulation material. This information can be used to select a predetermined size, i.e., the thickness of the thermal barrier in its uncompressed state.

[0076] Figure 9B This is a heat spread diagram showing the relationship between thermal resistance and cell area energy density, as well as the relationship between compression thickness and cell area energy density. Given one of these three variables, the values ​​of the other two properties can be determined using this heat spread diagram. In many cases, the cell area energy density is known due to the energy requirements of the system. Based on the known cell area density, multilayer materials can be selected to ensure the use of a barrier layer to suppress or minimize the propagation risk when the battery cell enters thermal runaway. In other cases, the multilayer material may have been pre-selected. In such other cases, the cell area energy density can be selected based on the known thermal resistance of the material to ensure suppression or minimization of propagation.

[0077] In use to generate Figure 9B In the specific example of the heat spread diagram, an aerogel material is used. In this example, the lighter shaded area at the top (above the dashed transition line) represents the region where runaway propagation occurs or almost never occurs. Generally, this heat spread diagram indicates that for temperatures up to approximately 14 kWh / m², runaway propagation is possible. 2The cell area energy density, a thermal resistivity of at least about 0.01, and a thickness factor of at least about 0.3 should effectively suppress or minimize the propagation of runaway cell structures. Optimal parameters for higher cell area densities can be determined using an epitaxial method on the thermal propagation map. In this paper, the thickness factor is defined as the ratio of the thickness of the multilayer material to the area energy density of the array. In this paper, the thermal resistivity is defined as the ratio of the thermal resistance of the multilayer material to the area energy density of the array.

[0078] Figure 14 Flowchart 100 outlines the process for designing the insulation system in a battery cell or module. In step 110, one or more battery cells or modules are assembled in an array with gaps between them. In step 120, the areal energy density of the array is calculated. Then, in step 130, the areal energy density is used to determine the thermal resistance and compressive thickness of the multilayer material. This thermal resistance and compressive thickness are selected to suppress or minimize heat propagation from runaway battery cells / modules.

[0079] Step 130 can be divided into two sub-steps. In one embodiment (shown on the left side of step 130), the thermal resistivity of the multilayer material is determined. Then, using the thermal resistivity of the multilayer material in conjunction with the areal energy density of the array, the thickness of the multilayer material required to suppress or minimize thermal runaway propagation is determined. This can be achieved by analyzing thermal propagation maps (e.g.,...). Figure 9B (As shown in the diagram) The minimum compressible thickness of the multilayer material is read to select the compressible thickness of the multilayer material that can suppress runaway propagation. Then, multilayer materials with this determined thickness are placed in the array.

[0080] In an alternative embodiment, step 130 can be performed by determining the thickness coefficient of the multilayer material that can be placed between the battery cells in the array. This determined thickness coefficient can be used to determine the thermal resistance of the multilayer material required to suppress or minimize heat propagation. In one embodiment, this can be determined from a heat propagation map (e.g., Figure 9B (As shown in the diagram) The minimum thermal resistance of the multilayer material is determined. The thermal resistance of the multilayer material is selected by determining that the thermal resistance of the multilayer material is greater than the minimum thermal resistance of the multilayer material required to suppress or minimize the propagation of thermal runaway. The multilayer material having the determined thermal resistance is then placed in the array.

[0081] In one embodiment, disposing of the multilayer material in and / or around the array includes forming the multilayer material independently of the array, and inserting battery cells adjacent to the array into the multilayer material. In another embodiment, disposing of the multilayer material in and / or around the array includes forming the multilayer material directly in and / or in situ in the array. The multilayer material can be formed in situ by spraying, coating, depositing, or filling the multilayer material in and / or around the array.

[0082] Figure 15 This diagram illustrates various configurations of battery cells and multilayer materials that can be used to suppress or minimize heat transfer. In a first configuration, the multilayer material is placed between individual battery cells or modules such that each cell / module is surrounded by the multilayer material. In a second configuration, multiple battery cells / modules are in contact with each other. The number of cells that can be stacked adjacent to each other without a barrier layer between them is based on the area energy density of the combined cell stack and the properties of the barrier layer (thermal resistance, etc.), i.e., based on... Figure 14 The method shown herein. The multilayer material surrounds the group of battery cells / modules to suppress or minimize the propagation of thermal runaway from any of the surrounded cells. This second configuration can be used in high-density energy systems where there is not much space available for thermal barriers (such as the multilayer material described herein). In a third configuration, the multilayer material is disposed between the individual battery cells / modules so that the multilayer material used to protect one of the battery cells / modules also protects adjacent battery cells / modules.

[0083] Please refer to Figure 9C The table shown provides various parameters and area energy density calculations for several square and bag-type units manufactured by different companies. Using the area energy density calculation and the compression faced between units, the thickness of the insulation material can be selected.

[0084] Used to generate Figure 9A and Figure 9B The thermal barrier is formed from an aerogel material available from Aspen Aerogels, located in Northborough, Massachusetts. The specific material used is marketed under the trade name PyroThin. ®This product is marketed as a thin, lightweight, high-temperature thermal insulation material. Beyond theory, Aspen Aerogels' aerogels offer advantages for at least three reasons. First, this particular aerogel material is elastic. Comparing its compressive stress with its compressive strain during loading and unloading events, only minimal hysteresis is observed. That is, this aerogel material is elastic. It is believed that the long silica-polymer chains together act as numerous elastic nanosprings, thus forming an elastic compression pad that absorbs mechanical energy with minimal fatigue or compressive deformation. Aspen Aerogels manufactures and markets reinforced M-grade materials that combine PyroThin... ® Product Name for Sale. M-grade materials are known to exhibit resistance to compressive deformation (≤ 5%) and fatigue. Another advantage of this particular material is its ability to withstand high temperatures, including up to 1400°C or higher. Generally, this particular aerogel material can withstand direct contact with a flame at 1000°C for more than 10 minutes. In other words, even after being exposed to a direct flame for up to 10 minutes, the aerogel material will not burn or even begin to decompose. Silica-based aerogels, including inorganic fibers, can have their thermal properties tuned. Therefore, the temperature resistance of this aerogel material can be adjusted to match unit behavior. Aspen Aerogel's silica-based aerogels provide beneficial thermal conductivity even when compressed, and therefore, according to this technology, can be advantageously used as insulation materials. It is not limited to theory that aerogels rely on trapped air to provide thermal advantages. Therefore, even when compressed, the aerogel material retains its thermal conductivity. This means that thinner barrier layers, lighter encapsulation, and larger unit coverage can be provided using insulation materials, thus offering these benefits to systems according to this technology.

[0085] This technology can also be applied to insulation materials that are not limited to single-layer materials. For example, in this technology, the thermal barrier disposed between units can have a multi-layer configuration. This multi-layer configuration includes one or more insulating layers that are sized to prevent heat transfer between units. In other words, although the thermal barrier includes several different layers in a multi-layer configuration, the thickness of the one or more insulating layers in their uncompressed state is selected using the methods and systems described with respect to single-layer embodiments and by utilizing knowledge of area energy density.

[0086] Including multilayer thermal barriers can add additional benefits such as mechanical strength, intumescent layers, and material encapsulation. The following description of multilayer materials can be used in this art to replace single-layer embodiments or to supplement a single-layer thermal barrier to the system. For example, some systems may include single-layer thermal barriers in some locations and multilayer thermal barriers in others. In other words, a single-layer thermal barrier is provided between certain adjacent units, while multilayer thermal barriers are provided between other adjacent units. In some embodiments, a single-layer thermal barrier is provided between adjacent units, and multilayer materials are used as thermal barriers around the edges or surfaces of the energy system.

[0087] This technology utilizes multilayer materials and systems including such multilayer materials to manage thermal runaway problems in energy storage systems. Exemplary embodiments include multilayer materials comprising at least one insulating layer, at least one compressible pad, and optionally one or more layers, possessing good heat dissipation properties, good fire resistance, flame retardancy, and / or abrasion resistance properties, and good performance for use as a thermal barrier. This disclosure further relates to a battery module or battery pack having one or more battery cells and the multilayer insulating material arranged in thermal communication with the battery cells.

[0088] One or more insulating layers of the multilayer materials disclosed herein may include an aerogel composition or a reinforced aerogel composition. Aerogel materials are known to have a thermal resistance approximately two to six times that of other common types of insulating materials (e.g., foams, glass fibers, etc.). Aerogels can provide effective shielding and thermal insulation without significantly increasing insulation thickness or adding extra weight. Aerogels are known to be a class of structures with low density, open-cell structure, large surface area, and nanoscale pore size.

[0089] The multilayer materials according to embodiments of this disclosure, and multilayer materials comprising aerogel compositions, provide good compressibility, compressive elasticity, and compliance properties. When used as a thermal barrier between cells within a battery module, the multilayer material provides resistance to compressive deformation to accommodate cell expansion due to degradation and expansion of the active material during the battery's charge / discharge cycles.

[0090] This disclosure further provides a battery module or battery pack, comprising: at least one battery cell; and a multilayer material according to embodiments disclosed herein, disposed on the battery cell or the battery module (e.g., on the surface of the at least one battery cell or the surface of the battery module). For example, the battery module or battery pack has an inner surface and an outer surface. In a particular embodiment, the multilayer material is located on the inner surface of the battery module or battery pack. In a particular embodiment, the multilayer material is located on the outer surface of the battery module or battery pack.

[0091] The multilayer material disclosed herein can have a variety of unique configurations, wherein more than one layer with good thermal and / or mechanical properties is arranged in a specific manner. Figure 10 This document illustrates an example multilayer material 400 according to an embodiment disclosed herein. In one embodiment, the multilayer material 400, used as a thermal barrier in an energy storage system, comprises: a core portion 700 including a layered assembly of insulating layers 470 and 480 and heat capacity layers 430, 440, and / or 450 alternately stacked in a direction perpendicular to its maximum surface; and an outer portion 600 disposed outside the core portion 700, each of the outer portions 600 having a sacrificial material layer including a compressible pad. The compressible pads 410 / 460 have a compressive modulus of about 1 MPa to 12 MPa. The encapsulation material layer 420 is selected from polymers, elastomers, or combinations thereof. The heat capacity layers 430, 440, and 450 have a specific heat capacity of at least about 200 J / (kg-K). The insulating layers 470 and 480 have a thermal conductivity throughout their thickness dimension of less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C.

[0092] In some embodiments, insulating layers 470 and 480 are made of the same material. In some embodiments, insulating layers 470 and 480 are made of different materials with different thermal and / or mechanical properties. In some embodiments, heat-capacity layers 430, 440, and 450 are made of the same material. In some embodiments, heat-capacity layers 430, 440, and 450 are made of different materials with different thermal and / or mechanical properties. Compressible pads 410 and 460 may also be made of different or the same materials.

[0093] Figure 11 This document illustrates a multilayer material 500 according to embodiments disclosed herein. In one embodiment, the multilayer material 500, used as a thermal barrier in an energy storage system, includes a core portion 700 comprising a layered assembly of insulating layers 470 and 480 and thermally conductive layers 530, 540, and 550 alternately stacked along a direction perpendicular to its maximum surface. An outer portion 600 is disposed outside the core portion 700. Each outer portion 600 has a sacrificial material layer including a compressible pad. The compressible pads 410 / 460 have a compressive modulus of about 1 MPa to 12 MPa. An encapsulating material layer 42 is selected from polymers, elastomers, or combinations thereof. The thermally conductive layers 530, 540, and 550 have a thermal conductivity of at least about 200 mW / mK along a plane dimension of the thermally conductive layer. Insulating layers 470 and / or 480 have thermal conductivity throughout the thickness dimension of the insulating layer that is less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C.

[0094] In some embodiments, thermally conductive layers 530, 540, and 550 are made of the same material. In some embodiments, thermally conductive layers 530, 540, and 550 are made of different materials with different thermal and / or mechanical properties.

[0095] In some embodiments, the encapsulation material layer 420 is sandwiched between the core portion 700 and a sacrificial material layer having at least one compressible pad 410 and / or 460, such as Figure 10 and Figure 11 As shown in the diagram. In some embodiments, the sacrificial material layer having at least one compressible pad 410 and / or 460 is sandwiched between the core portion 700 and the encapsulation material layer 420.

[0096] The multilayer material according to the embodiments disclosed herein may have an average thickness in the range of about 2 mm to about 10 mm in its uncompressed state. When exposed to external mechanical loads, such as loads applied to the material between cells during the initial assembly of a battery module (e.g., 1 MPa or less), the average thickness of the multilayer material may decrease.

[0097] exist Figure 12A In the example configuration of the multilayer material shown, the multilayer material 800 used as a thermal barrier in an energy storage system includes: a core layer comprising a compressible pad 410 having a compressive modulus of about 1 MPa to about 12 MPa (e.g., 1.5 MPa, 2 MPa, 4 MPa, 5 MPa, 6 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 11.5 MPa); and two insulating layers 470 and 480 having a thermal conductivity of less than about 50 mW / mK at 25°C and less than about 60 mW / mK throughout the thickness dimension of the insulating layer. The core layer is sandwiched between the two insulating layers 470 and 480, wherein the multilayer material may be selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof.

[0098] exist Figure 12BIn the example configuration of the multilayer material shown, the multilayer material 810 used as a thermal barrier in an energy storage system includes a core layer of a compressible pad 410 having a compressive modulus of about 1 MPa to about 12 MPa, and two thermally conductive layers 530 and 540. The multilayer material 801 also includes two insulating layers 470 and 480 having a thermal conductivity through the thickness dimension of the insulating layer that is less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C, and the core layer is sandwiched between the two insulating layers 470 and 480, while the at least one thermally conductive layer has an in-plane thermal conductivity of at least about 200 mW / mK, and wherein the multilayer material is selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof.

[0099] exist Figure 12C In the exemplary embodiment shown, the multilayer material 820 used as a thermal barrier in an energy storage system includes a core layer of a compressible pad 410 having a compressive modulus of about 1 MPa to about 12 MPa, and two thermal capacity layers 430 and 440. The core layer is sandwiched between two insulating layers 470 and 480, the insulating layers having a thermal conductivity throughout their thickness dimension of less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C. The thermal capacity layers have a specific heat capacity of at least about 200 J / (kg-K). The multilayer material may be selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof.

[0100] In such Figure 12D In the exemplary embodiment shown, the multilayer material 830 used as a thermal barrier in an energy storage system includes a core layer of a compressible pad 410 having a compressive modulus of about 1 MPa to about 12 MPa, and two thermal capacity layers 430 and 440. Two insulating layers 470 and 480 sandwiching the core layer have a thermal conductivity throughout the thickness dimension of the insulating layer that is less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C. The thermal capacity layer has a specific heat capacity of at least about 200 J / (kg-K). The multilayer material 830 further includes two additional thermal capacity layers 435 and 445 disposed on the outer surfaces of each of the insulating layers 470 and 480. The multilayer material may be selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof.

[0101] exist Figure 12EIn the example configuration of the multilayer material shown, the multilayer material 840 used as a thermal barrier in an energy storage system includes a core layer comprising two compressible pads 410 and 460 (each having a compressive modulus of about 1 MPa to about 12 MPa) and a heat capacity layer 430. Two insulating layers 470 and 480 sandwiching the core layer have a thermal conductivity throughout the thickness dimension of the insulating layer that is less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C. The heat capacity layer has a specific heat capacity of at least about 200 J / (kg-K). The multilayer material may be selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof. The heat capacity layer 430 is sandwiched between the two compressible pads 410 and 460.

[0102] exist Figure 13 In the example configuration of the multilayer material shown, the multilayer material 900 used as a thermal barrier in an energy storage system includes a core layer and an outer portion. The core layer includes an insulating layer 470, and the outer portion includes thermally conductive layers 530 and 540. In the illustrated embodiment, the thermally conductive layers 530 and 540 are substantially L-shaped. The vertical portion of the L-shaped thermally conductive layer is spaced apart from the insulating layer. During use, the vertical portion of the L-shaped thermally conductive layer is in thermal or physical contact with the battery cells or battery modules (570, 575, 580). The horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer 470 and the heat transfer element 590. The use of the L-shaped thermally conductive layer increases the surface area of ​​contact between the thermally conductive layer and the battery cells or modules and any heat transfer element. During use, heat from one or more of the battery cells or battery modules is conducted through the thermally conductive layer to the heat transfer element 590. Therefore, heat from the battery cells or battery modules is removed through the heat transfer element. The heat transfer element may be a cooling plate. The example cooling plate includes fluid transport (liquid or gas) to remove heat from the heat transfer element during use.

[0103] In one embodiment, one or more of the following are provided between the vertical portion of the L-shaped thermally conductive layers 530, 540 and the insulating layer 470: an encapsulation layer (420, 425), a sacrificial material layer (510, 515), and a heat-capacitance layer (430, 435), such as... Figure 13 As shown in the diagram. The sacrificial layer 510 may include a compressible pad having a compressive modulus of about 1 MPa to 12 MPa. The insulating layer 470 has a thermal conductivity throughout its thickness dimension of less than about 50 mW / mK at 25°C and less than about 60 mW / mK at 600°C. The heat capacity layers (430, 435) have a specific heat capacity of at least about 200 J / (kg-K). The insulating layer may be selectively encapsulated in an encapsulation material 420 selected from at least one of polymers, elastomers, or combinations thereof. In some embodiments, the encapsulation layer may include a metal layer.

[0104] During use, each of these layers will act as a barrier layer to prevent heat from the runaway cell from heating other cells. The heat-capacity layer will absorb the initial heat from the runaway cell. Heat passing through the heat-capacity layer will impact the sacrificial layer, which will absorb heat as the layer decomposes. Finally, the encapsulation layer will also act as a barrier layer to reduce the amount of particulate matter impacting the insulation layer. In one embodiment, the insulation barrier extends at least partially into the heat exchange element 590. Placing the insulation layer in the heat exchange element helps reduce heat transfer from the battery cell or module undergoing thermal runaway. For example, in some embodiments, heat from a thermal runaway event will overwhelm the cooling effect of the heat exchange element. Therefore, heat from the runaway cell or module may be conducted to other battery cells or modules through the heat exchange element. This portion of the insulation barrier extending into the heat exchange element inhibits the heat from reaching adjacent battery cells or modules.

[0105] Insulation layer The insulating layer of the multilayer material described herein is responsible for reliably controlling the heat flow in heat-generating portions of a small space, thereby providing safety and preventing fire propagation for such products in the electronics, industrial, and automotive technology sectors. Insulating layers with superior compressibility properties can be used to meet these requirements. In many embodiments of this disclosure, the insulating layer itself, or other layers combined with the multilayer material, also act as a flame / fire diversion layer. For example, an insulating layer (such as an aerogel layer) combined with a flame-retardant layer (such as a metal or mica layer) can protect the underlying layer from flames and / or hot gases, as well as flames / hot gases carrying particulate materials (e.g., materials that may be ejected from the LIB during a thermal runaway event). As another example, the insulating layer may itself be resistant to flames and / or hot gases, as well as flames / hot gases carrying particulate materials. An insulating layer (e.g., mica, microporous silica, aerogel) combined with a flame-retardant layer can act as a flame / fire diversion layer. Insulating layers, including aerogels (such as those disclosed in the embodiments herein), are durable and easy to handle, have good resistance to heat and fire propagation, while minimizing the thickness and weight of the materials used, and have good compressibility, compressive elasticity and conformability properties.

[0106] Aerogels are a class of porous materials with open pores, comprising an interconnected framework within which a corresponding network of pores is integrated, and the interstitial phase within this network is primarily composed of gas, such as air. Aerogels are typically characterized by low density, high porosity, large surface area, and small pore size. Aerogels can be distinguished from other porous materials by their physical and structural properties.

[0107] Therefore, in some embodiments, the insulating layer of the multilayer material of this disclosure comprises aerogel. In some embodiments, the insulating layer may further comprise a material selected from the group consisting of mica, microporous silica, ceramic fibers, rock wool, and combinations thereof. In some cases, the insulating layer does not have aerogel. In some embodiments, the insulating layer may comprise a material selected from the group consisting of mica, microporous silica, ceramic fibers, rock wool, and combinations thereof.

[0108] In a particular embodiment, the insulating layer of this disclosure has a thermal conductivity throughout the thickness dimension of the insulating layer in the range of about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or any two of these values ​​at 25°C. In a particular embodiment, the insulating layer of this disclosure has a thermal conductivity throughout the thickness dimension of the insulating layer in the range of about 60 mW / mK or less, about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or in any two of these values ​​at 600°C.

[0109] Under loads up to about 5 MPa, the insulating layer of this disclosure (e.g., an insulating layer comprising aerogel) can maintain its thermal conductivity (typically measured in mW / mK) unchanged or increase it by a negligible amount. In a particular embodiment, under loads up to about 5 MPa, the insulating layer of this disclosure has a thermal conductivity throughout the thickness dimension of the insulating layer within a range of about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or any two of these values, at 25°C. The thickness of the aerogel insulating layer may be reduced due to the load borne by the aerogel insulating layer. For example, under loads ranging from approximately 0.50 MPa to 5 MPa, the thickness of the aerogel insulation layer can be reduced by 50% or less, 40% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 5% or less, or in any two of these values. While the thermal resistance of the insulation layer including the aerogel may decrease with decreasing thickness, the thermal conductivity may remain constant or increase by an insignificant amount.

[0110] In certain embodiments, the insulating layer of this disclosure may have a heat of combustion of about 750 cal / g or less, about 717 cal / g or less, about 700 cal / g or less, about 650 cal / g or less, about 600 cal / g or less, about 575 cal / g or less, about 550 cal / g or less, about 500 cal / g or less, about 450 cal / g or less, about 400 cal / g or less, about 350 cal / g or less, about 300 cal / g or less, about 250 cal / g or less, about 200 cal / g or less, about 150 cal / g or less, about 100 cal / g or less, about 50 cal / g or less, about 25 cal / g or less, about 10 cal / g or less, or in any two of these values. An insulation layer having an improved heat of combustion (HOC) relative to a reference insulation layer will have a lower HOC value. In a particular embodiment of this disclosure, the HOC of the insulation layer is improved by incorporating a fire-retardant additive into the insulation layer.

[0111] In certain embodiments, the insulating layer of this disclosure has a thermal decomposition onset temperature of about 300°C or higher, about 320°C or higher, about 340°C or higher, about 360°C or higher, about 380°C or higher, about 400°C or higher, about 420°C or higher, about 440°C or higher, about 460°C or higher, about 480°C or higher, about 500°C or higher, about 515°C or higher, about 550°C or higher, about 600°C or higher, or within any two of these values. In the context herein, for example, a thermal decomposition onset temperature of a first composition that is higher than that of a second composition will be considered an improvement of the first composition relative to the second composition. It is contemplated herein that the thermal decomposition onset temperature of a composition or material increases when one or more fire-retardant additives are added, compared to a composition that does not contain any fire-retardant additives.

[0112] The term "flexural modulus" or "flexural elastic modulus" is a measure of a material's stiffness / resistance to bending when a force is applied perpendicular to the long side of the sample—a test known as the three-point bending test. The flexural modulus represents a material's ability to bend. It is expressed by the slope of the initial linear portion of the stress-strain curve and is calculated by dividing the stress change by the corresponding strain change. Therefore, the stress-to-strain ratio is a measure of the flexural modulus. The international standard unit for flexural modulus is Pascal (Pa or N / m). 2 Or m-1.kg.s-2). The actual unit used is megapascal (MPa or N / mm). 2 or gigapascals (GPa or kN / mm) 2 In the United States, this is expressed in pounds (forces) per square inch (psi). In certain embodiments, the insulating layer of this disclosure has a flexural modulus of about 8 MPa or less, about 7 MPa or less, about 6 MPa or less, about 5 MPa or less, about 4 MPa or less, or about 3 MPa or less. Preferably, the insulating layer of this disclosure (e.g., aerogel) has a flexural modulus of about 2 MPa to about 8 MPa.

[0113] As described above, the compressibility and elasticity properties of the materials between the cells or battery modules and battery packs are important to accommodate the expansion of the cells during their lifespan. In a particular embodiment, the insulating layer or the multilayer material including the insulating layer (i) is compressible to at least 50%, preferably at least 65%, and most preferably at least 80% of its initial or uncompressed thickness, and (ii) has sufficient elasticity to recover to at least 70%, preferably at least 75%, and most preferably at least 80% of its initial or uncompressed thickness after a few seconds of compression.

[0114] In a particular embodiment, the compressive modulus of the insulating layer (e.g., a layer comprising aerogel), the compressible component of the multilayer material comprising the insulating layer, or the multilayer material as a whole, is about 1 MPa, about 2 MPa, about 3 MPa, about 4 MPa, about 5 MPa, about 6 MPa, about 7 MPa, about 8 MPa, about 9 MPa, about 10 MPa, about 11 MPa, about 12 MPa, or in any two of these values.

[0115] aerogel The aerogel of the present invention can be organic, inorganic, or a mixture thereof. In some embodiments, the aerogel comprises a silica-based aerogel. The insulating layer of the multilayer material comprising the aerogel further comprises a reinforcing material. The reinforcing material can be any material that provides elasticity, consistency, or structural stability to the aerogel material. Well-known examples of reinforcing materials include, but are not limited to, open-cell macroporous framework reinforcing materials, closed-cell macroporous framework reinforcing materials, open-cell membranes, honeycomb reinforcing materials, polymeric reinforcing materials, and fiber reinforcing materials, such as discrete fibers, woven materials, nonwoven materials, needle-punched nonwoven materials, cotton wool, nets, mats, and felts.

[0116] The reinforcing material can be selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. The inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof.

[0117] In some embodiments, the reinforcing material may include a reinforcing layer comprising multiple material layers. For example, the multiple material layers may be bonded together. In an exemplary embodiment, at least one of the multiple layers may include a first material, and at least another layer of the multiple layers may include a second material. The first material and the second material may have the same or different material properties. For example, the first material may be more compressible than the second material. As another example, the first material may include a closed unit, and the second material may include an open unit.

[0118] Aerogels are described as frameworks of interconnected structures, typically composed of interconnected oligomers, polymers, or colloidal particles. Aerogel frameworks can be made from a range of precursor materials, including inorganic precursor materials (e.g., precursors for manufacturing silica-based aerogels); organic precursor materials (precursors for manufacturing carbon-based aerogels); mixed inorganic / organic precursor materials; and combinations thereof. In the context of this disclosure, the term "amalgam aerogel" refers to an aerogel manufactured from a combination of two or more different gel precursors; the corresponding precursors are referred to as "mixed precursors."

[0119] Inorganic aerogel Inorganic aerogels are typically formed from metal oxides or metal alkoxides. These metal oxides or alkoxides can be based on oxides or alkoxides of any metal capable of forming oxides. Such metals include, but are not limited to, silicon, aluminum, titanium, zirconium, hafnium, yttrium, vanadium, and cerium. Inorganic silica aerogels are traditionally produced through the hydrolysis and condensation of silica-based alkoxides (e.g., tetraethoxysilanes) or through the gelation of silicic acid or water glass. Other relevant inorganic precursor materials for the synthesis of silica-based aerogels include, but are not limited to, metal silicates, such as sodium silicate or potassium silicate, alkoxysilanes, partially hydrolyzed alkoxysilanes, tetraethoxysilanes (TEOS), partially hydrolyzed TEOS, condensation polymers of TEOS, tetramethoxysilanes (TMOS), partially hydrolyzed TMOS, condensation polymers of TMOS, tetrapropoxysilanes, partially hydrolyzed and / or condensation polymers of tetrapropoxysilanes, polyethyl silicate, partially hydrolyzed polyethyl silicate, monomeric alkylalkoxysilanes, bis(trialkoxyalkyl) or arylsilanes, polyhedral silsesquioxanes, or combinations thereof.

[0120] In certain embodiments of this disclosure, pre-hydrolyzed TEOS (e.g., Silbond H-5 (SBH5, Silbond Corporation), hydrolyzed at a water / silica ratio of approximately 1.9-2) may be commercially available or may be further hydrolyzed prior to incorporation into the gelation process. Partially hydrolyzed TEOS or TMOS (e.g., polyethylene silicate (Silbond 40) or polymethyl silicate) may also be commercially available or may be further hydrolyzed prior to incorporation into the gelation process.

[0121] Inorganic aerogels may also include gel precursors comprising at least one hydrophobic group, such as alkyl metal alkoxides, cycloalkyl metal alkoxides, and aryl metal alkoxides, which can impart or improve specific properties in the gel, such as stability and hydrophobicity. Inorganic silica aerogels may specifically include hydrophobic precursors, such as alkylsilanes or arylsilanes. Hydrophobic gel precursors can be used as primary precursor materials to form the framework of the gel material. However, hydrophobic gel precursors are more often used as co-precursors to bind simple metal alkoxides during the formation of hybrid aerogels. Hydrophobic inorganic precursor materials used for the synthesis of silica-based aerogels include, but are not limited to, trimethylmethoxysilane (TMS), dimethyldimethoxysilane (DMS), methyltrimethoxysilane (MTMS), trimethylethoxysilane, dimethyldiethoxysilane (DMDS), methyltriethoxysilane (MTES), ethyltriethoxysilane (ETES), diethyldiethoxysilane, dimethyldiethoxysilane (DMDES), ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane (PhTES), hexamethyldisilazane, and hexaethyldisilazane. Any derivative of any of the above precursors can be used, and specifically, other chemical groups for a particular polymerization can be added to or crosslinked to one or more of the above precursors.

[0122] Aerogels can also be treated to impart or improve hydrophobicity. Hydrophobic treatments can be applied to sol-gel solutions, wet gels prior to liquid extraction, or aerogels after liquid extraction. Hydrophobic treatments are particularly common in the fabrication of metal oxide aerogels, such as silica aerogels. Examples of hydrophobic treatments of gels are discussed in more detail below, particularly in the context of treating wet silica gels. However, the specific examples and figures provided herein are not intended to limit the scope of this disclosure to any particular type of hydrophobic treatment step or aerogel matrix. This disclosure may include any gel or aerogel known to those skilled in the art, and related methods for hydrophobic treatment of aerogels (in wet or dry aerogel form).

[0123] Hydrophobic treatment is performed by reacting the hydroxyl groups on the gel (e.g., the silanol groups (Si-OH) present on the framework of a silica gel) with the functional groups of a hydrophobic agent. The resulting reaction transforms the silanol groups and the hydrophobic agent into hydrophobic groups on the framework of the silica gel. The hydrophobic agent compound can react with the hydroxyl groups on the gel according to the following reaction: RNMX4-N (hydrophobic agent) + MOH (silanol) → MOMRN (hydrophobic group) + HX. Hydrophobic treatment can occur on both the outer macroscopic surface of the silica gel and the inner pore surfaces within the porous network of the gel.

[0124] The gel can be immersed in a mixture of a hydrophobic agent and an optional hydrophobic treatment solvent (in which the hydrophobic agent is soluble and miscible with the gel solvent in the wet gel). A wide range of hydrophobic treatment solvents can be used, including solvents such as methanol, ethanol, isopropanol, xylene, toluene, benzene, dimethylformamide, and hexane. The hydrophobic agent, in liquid or gaseous form, can also be directly contacted with the gel to impart hydrophobicity.

[0125] The hydrophobic treatment process may include mixing or stirring to help the hydrophobic agent penetrate the wet gel. The hydrophobic treatment process may also include altering other conditions, such as temperature and pH, to further enhance and optimize the treatment reaction. After the reaction is complete, the wet gel is washed to remove unreacted compounds and reaction byproducts.

[0126] Hydrophobic agents used for hydrophobic treatment of aerogels are typically compounds having the formula RNMX4-N; wherein M is a metal; R is a hydrophobic group, such as CH3, CH2CH3, C6H6, or similar hydrophobic alkyl, cycloalkyl, or aryl moiety; and X is a halogen, typically Cl. Specific examples of hydrophobic agents include, but are not limited to, trimethylchlorosilane (TMCS), triethylchlorosilane (TECS), triphenylchlorosilane (TPCS), dimethylchlorosilane (DMCS), dimethyldichlorosilane (DMDCS), etc. Hydrophobic agents may also have the formula: Y(R3M)2; wherein M is a metal; Y is a bridging group, such as NH or O; and R is a hydrophobic group, such as CH3, CH2CH3, C6H6, or similar hydrophobic alkyl, cycloalkyl, or aryl moiety. Specific examples of such hydrophobic agents include, but are not limited to, hexamethyldisilazane [HMDZ] and hexamethyldisiloxane [HMDSO]. Hydrophobic agents may further include compounds having the formula RNMV4-N, where V is a reactive or leaving group other than a halogen. Specific examples of such hydrophobic agents include, but are not limited to, vinyltriethoxysilane and vinyltrimethoxysilane.

[0127] The hydrophobic treatment disclosed herein can also be performed during the removal, displacement, or drying of the liquid in the gel. In certain embodiments, the hydrophobic treatment can be performed in a supercritical fluid environment (e.g., but not limited to supercritical carbon dioxide) and can be combined with drying or extraction steps.

[0128] Organic aerogel Organic aerogels are typically formed from carbon-based polymeric precursors. These polymeric materials include, but are not limited to, resorcinol-formaldehyde (RF), polyimide, polyacrylate, polymethyl methacrylate, acrylate oligomers, polyoxyethylene, polyurethane, polyphenols, polybutadiene, trialkoxysilane-terminated polydimethylsiloxane, polystyrene, polyacrylonitrile, polyfurfural, melamine-formaldehyde, cresol-formaldehyde, phenol-furfural, polyethers, polyols, polyisocyanates, polyhydroxybenzene, polyvinyl alcohol dialdehyde, polycyanurate, polyacrylamide, various epoxy resins, agar, agarose, chitosan, and combinations thereof. For example, organic RF aerogels are typically prepared by sol-gel polymerization of resorcinol or melamine with formaldehyde under alkaline conditions.

[0129] Organic / inorganic mixed aerogel Organic / inorganic hybrid aerogels are primarily composed of organically modified silica (“ormosil”) aerogels. These ormosil materials include organic components covalently bonded to the silica network. Ormosil is typically formed using the conventional alkoxide precursor Y(OX)4 through the hydrolysis and condensation of the organically modified silane R-Si(OX)3. In these formulas, X can represent, for example, CH3, C2H5, C3H7, C4H9; Y can represent, for example, Si, Ti, Zr, or Al; and R can be any organic fragment, such as methyl, ethyl, propyl, butyl, isopropyl, methacrylate, acrylate, vinyl, epoxide, etc. The organic component in the ormosil aerogel can also be dispersed throughout the silica network or chemically bonded to it.

[0130] In certain embodiments, the aerogels of this disclosure are primarily inorganic silica aerogels formed from prepolymerized silica precursors (preferably oligomers), or hydrolyzed silicates formed from silanol salts in an alcohol solvent. In certain embodiments, such prepolymerized silica precursors or hydrolyzed silicates may be formed in situ from other precursors or silicates (e.g., alkoxysilanes or water glass). However, the invention as a whole can be implemented using any other aerogel compositions known to those skilled in the art, and is not limited to any single precursor material or mixture of precursor materials.

[0131] Macropores As described above, the aerogel composition according to embodiments of the present disclosure may include an aerogel framework comprising macropores. Without limitation to any operational theory, the presence of macropores within the aerogel framework allows for the compression of the aerogel composition (e.g., enhances the aerogel composition) while maintaining or even improving thermal properties, such as reducing thermal conductivity. For example, the macropores may be deformed, compressed, or otherwise reduced in size by compression of the composition, thereby reducing the thickness of the composition under load. However, as the macropores deform, they effectively become smaller pores. Therefore, when the macropores deform, the heat transfer path within the aerogel framework can become more tortuous, thereby improving thermal properties, such as reducing thermal conductivity. In the context of this disclosure, “mesopores” refers to pores with an average pore diameter in the range of about 2 nm to about 50 nm. Aerogel frameworks are typically mesopores (i.e., primarily comprising pores with an average diameter from about 2 nm to about 50 nm). In certain embodiments, the aerogel framework of the aerogel composition of the present disclosure may include macropores. In the context of this disclosure, “macropores” refers to pores with an average pore diameter greater than about 50 nm. The aerogel framework may include macropores and mesopores. For example, at least 10% of the pore volume of the aerogel framework may be composed of macropores, at least 5% of the pore volume of the aerogel framework may be composed of macropores, at least 75% of the pore volume of the aerogel framework may be composed of macropores, at least 95% of the pore volume of the aerogel framework may be composed of macropores, or at least 100% of the pore volume of the aerogel framework may be composed of macropores. In some specific embodiments, the aerogel framework may be a macroporous aerogel framework, such that the majority of its pore volume is composed of macropores. In some cases, the macroporous aerogel framework may also include micropores and / or mesopores. In some embodiments, the average pore size (diameter) of the pores in the aerogel framework may be greater than 50 nm, greater than 50 nm to 5000 nm, 250 nm to 2000 nm, 500 nm to 2000 nm, 500 nm to 1400 nm, or 1200 nm. In a particular embodiment, the average pore size (diameter) may be greater than 50 nm, greater than 50 nm to 1000 nm, preferably 100 nm to 800 nm, and more preferably 250 nm to 750 nm.

[0132] Uniform and non-uniform pore size distribution In some embodiments, the pore size variation within the aerogel framework can be uniformly distributed along the aerogel framework. For example, the average pore size can be substantially the same throughout the aerogel framework.

[0133] In other embodiments, the pore size variation within the aerogel frame may be non-uniformly distributed along the aerogel frame. For example, the average pore size may differ in specific regions of the aerogel frame. In some exemplary embodiments, the average pore size may be larger on the upper surface, lower surface, or a region of both surfaces of the aerogel frame. For example, macropores may be distributed within the composition such that the ratio of macropores to mesopores on the upper surface is greater than that on the lower surface, the ratio on the lower surface is greater than that on the upper surface, or the ratio on both surfaces is greater than that in the intermediate region between the upper and lower surfaces. As another example, macropores may be distributed within the composition such that the ratio of macropores to mesopores near the upper surface is greater than that near the lower surface, the ratio near the lower surface is greater than that near the upper surface, or the ratio near both surfaces is greater than that in the intermediate region between the upper and lower surfaces. In other embodiments, the average pore size may be larger in the intermediate region between the upper and lower surfaces of the aerogel frame.

[0134] Macropore formation Macropores can be formed during the manufacture of the aerogel composition. For example, macropore formation can be induced in the gel precursor material during the conversion to a gel composition. In some embodiments, macropore formation can be achieved by inducing, for example, spinodal decomposition of the gel precursor solution. Alternatively, macropore formation can be induced by adding one or more foaming agents.

[0135] Compared to mesopores and / or micropores, macropores can be formed in the resulting aerogel framework by selecting process conditions that are favorable for the formation of macropores. The number of macropores can be adjusted by implementing any one, any combination of, or all of the following variables: (1) polymerization solvent; (2) polymerization temperature; (3) polymer molecular weight; (4) molecular weight distribution; (5) copolymer composition; (6) number of branches; (7) number of crosslinks; (8) branching method; (9) crosslinking method; (10) method for forming gel; (11) type of catalyst used to form gel; (12) chemical composition of catalyst used to form gel; (13) amount of catalyst used to form gel; (14) gel forming temperature; (15) type of gas flowing through the material during gel formation; (16) gas flow rate through the material during gel formation; (17) atmospheric pressure during gel formation; (18) removal of dissolved gases during gel formation; (19) solid additives present in the resin during gel formation; (20) time of gel formation process; (21) matrix used for gel formation; (22) type of one or more solvents used in each step of the solvent replacement process; (23) solvent (24) The composition of one or more solvents used in each step of the solvent replacement process; (25) The amount of time used in each step of the solvent replacement process; (26) The residence time of the component in each step of the solvent replacement process; (27) The flow rate of the solvent used for solvent replacement; (28) The flow type of the solvent used for solvent replacement; (29) The stirring rate of the solvent used for solvent replacement; (30) The temperature used in each step of the solvent replacement process; (31) The ratio of the volume of the solvent used for solvent replacement to the volume of the component; (32) The drying method; (33) The temperature of each step in the drying process; (34) The pressure of each step in the drying process; (35) The composition of the gas used in each step of the drying process; (36) The gas flow rate during each step of the drying process; (37) The component temperature during each step of the drying process; (38) The presence of a shell surrounding the component during each step of the drying process; (39) The type of shell surrounding the component during drying; and / or (40) The solvent used in each step of the drying process. Multifunctional amines and diamine compounds can be added as solids (pure or dissolved in a suitable solvent) individually or together in one or more portions. In other aspects, a method of manufacturing an aerogel may include the steps of: (a) providing a multifunctional amine compound and at least one diamine compound to a solvent to form a solution; (b) providing at least one dianhydride compound to the solution of step (a) under conditions sufficient to form a branched polymer matrix solution, wherein the branched polymer matrix is ​​dissolved in the solution; and (c) placing the branched polymer matrix solution under conditions sufficient to form an aerogel with an open-pore structure. Macropores appearing in the resulting aerogel framework can be formed in the manner described above.In a preferred and non-limiting aspect, the formation of macropores, relative to smaller mesopores and micropores, can be primarily controlled by manipulating polymer / solvent kinetics during gel formation.

[0136] As described above, the aerogel composition according to embodiments of the present disclosure may include an aerogel framework and a reinforcing material, wherein at least a portion of the reinforcing material does not contain aerogel. For example, the aerogel framework may extend partially through the thickness of the reinforcing material. In such embodiments, portions of the reinforcing material (e.g., OCMF, fibers, or combinations thereof) may include aerogel material, and portions may not have aerogel. For example, in some embodiments, the aerogel extends through about 90% of the thickness of the reinforcing material, through about 50% to about 90% of the thickness of the reinforcing material, through about 10% to about 50% of the thickness of the reinforcing material, or through about 10% of the thickness of the reinforcing material.

[0137] Not limited to any particular operating theory, aerogel compositions (wherein at least a portion of the reinforcing material does not contain aerogel) can provide good compressibility, compressive elasticity, and compliance properties. For example, the properties of the reinforcing material can be selected to provide sufficient reinforcement and support for thermal properties in regions containing aerogel, and sufficient compressibility, compressive elasticity, and / or compliance in regions without aerogel. The aerogel-containing portion of the reinforced aerogel composition can provide the desired thermal conductivity, for example, less than about 25 mW / m*K, while the aerogel-free reinforcing portion can provide or improve the desired physical properties, such as compressibility.

[0138] In some embodiments, a reinforced aerogel composition (where at least a portion of the reinforcing material does not contain aerogel) can be formed using the methods disclosed herein, wherein the reinforcing material is combined with an amount of precursor solution sufficient to partially fill the reinforcing material with the precursor solution. For example, the volume of the precursor may be smaller than the volume of the reinforcing material, such that the precursor extends only partially through the reinforcing material. Upon drying, the resulting reinforced aerogel composition will comprise an aerogel framework extending to less than the full thickness of the reinforcing material, as described above. In other embodiments, a reinforced aerogel composition (where at least a portion of the reinforcing material does not contain aerogel) can be formed by removing a surface aerogel layer from the aerogel composition.

[0139] In some embodiments, the reinforced aerogel composition (where at least a portion of the reinforcing material does not contain aerogel) may be formed using a reinforcing material having mixed properties along the thickness of the reinforcing material. For example, the reinforcing material may comprise multiple layers, each with different properties, such as differences in average pore size, material composition, closed-cell, open-cell, surface treatment, or combinations thereof. The multiple layers may be bonded to each other, for example using adhesives, by flame bonding, or by other suitable methods or mechanisms (such as those discussed herein). The different properties of the reinforcing material may provide different aerogel distributions in the layers. For example, the open-cell portions of the reinforcing material may comprise an aerogel framework, while the closed-cell portions remain substantially aerogel-free. Similarly, other material properties of the reinforcing material or its layers may determine the aerogel distribution within the reinforcing material and thus within the reinforced aerogel composition.

[0140] In some exemplary embodiments, a reinforced aerogel composition (where at least a portion of the reinforcing material does not contain aerogel) can be formed using the methods disclosed herein, wherein the properties of the reinforcing material or layer control or influence the amount of precursor solution filling the material or layer (e.g., during a casting process) to provide partial filling of the reinforcing material with the precursor solution. For example, one layer of the reinforcing material may have open pores, and another layer of the reinforcing material may have closed pores. When the precursor solution is combined with such a reinforcing material, the gel precursor solution can penetrate into the open pores of the layer without significantly penetrating into the closed pores of the other layer. When such a composition is dried, the resulting reinforced aerogel composition may include portions that do not contain aerogel (e.g., the closed-pore layer), while another portion (e.g., the open-pore layer) contains aerogel.

[0141] In some embodiments, the additives disclosed herein (e.g., heat-absorbing additives, light-shielding additives, fire-retardant additives, or other additives) may be non-uniformly dispersed in the reinforced aerogel composition. For example, the additive material may vary with the thickness of the aerogel composition or along its length and / or width. For example, the additive may accumulate on one side of the aerogel composition. In some embodiments, the one or more additive materials may be concentrated in one layer of the aerogel composition or provided as a separate layer consisting essentially of additives adjacent to or attached to the composition. For example, a thermal control may include a layer consisting essentially of a heat-absorbing material (e.g., gypsum, sodium bicarbonate, magnesium oxide-based cement). In other exemplary embodiments, the aerogel composition may also include at least one additional material layer located within the composition or as a topcoat. For example, this layer may be a layer selected from the group consisting of polymer flakes, metal flakes, fiber flakes, highly oriented graphite materials (e.g., pyrolytic graphite flakes), and fabric flakes. In some embodiments, the overlay layer may be attached to the composition, for example, by an adhesive mechanism selected from the group consisting of aerosol adhesives, urethane adhesives, acrylate adhesives, hot melt adhesives, epoxy resins, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, the overlay layer may be attached to the composition by a non-adhesive mechanism (e.g., a mechanism selected from the group consisting of flame bonding, needle punching, sewing, sealing bags, rivets, buttons, clips, wrapping, brackets, and combinations thereof). In some embodiments, any combination of the above-described adhesive and non-adhesive mechanisms may be used to attach the overlay layer to the composition.

[0142] Powdered aerogel composition As described herein, aerogel compositions or composites may include materials to incorporate aerogel microparticles, particles, granules, microbeads, or powders into solid or semi-solid materials, such as in combination with binders, such as adhesives, resins, cements, foams, polymers, or similar solid or cured materials. For example, an aerogel composition may include reinforcing materials, aerogel particles, and optionally a binder. In exemplary embodiments, a slurry comprising aerogel particles and at least one wetting agent may be provided. For example, the aerogel particles may be coated or wetted with at least one wetting agent (e.g., a surfactant or dispersant). The aerogel particles may be fully wetted, partially wetted (e.g., surface-wetted), or present in the slurry. Preferred wetting agents are volatile to allow proper restoration of the hydrophobicity of the hydrophobic aerogel particles. If the wetting agent remains on the surface of the aerogel particles, the residual wetting agent may promote the overall thermal conductivity of the composite material. Therefore, preferred wetting agents are removable wetting agents, for example, through evaporation, with or without decomposition, or other means. Generally, any wetting agent compatible with the aerogel can be used.

[0143] wetting agent A slurry or aerogel coated with a wetting agent can serve as a convenient method for incorporating hydrophobic aerogels into a variety of materials, such as other aqueous fluids, slurries, adhesives, and bonding agents, which can be selectively cured to form solid materials, fibers, metallized fibers, discrete fibers, woven materials, nonwoven materials, needle-punched nonwoven materials, wadding, webs, mats, felts, and combinations thereof. An aerogel wetted with at least one wetting agent, or a slurry containing an aerogel and at least one wetting agent, facilitates the incorporation and uniform distribution of the hydrophobic aerogel. Wet web-forming processes (e.g., those described in U.S. Patent Nos. 9,399,864, 8,021,583, 7,635,411, and 5,399,422, all incorporated herein by reference in their entirety) use an aqueous slurry to disperse aerogel particles, fibers, and other additives. The slurry can then be dehydrated to form a layer consisting of aerogel particles, fibers, and additives, which can be dried and selectively calendered to produce an aerogel complex.

[0144] Aerogel particles and additives In other embodiments, the aerogel composition may include aerogel particles, at least one inorganic matrix material, and optionally fibers, auxiliary materials, additives, and other inorganic binders. In some embodiments, the inorganic matrix material may include layered silicates, such as naturally occurring layered silicates like kaolin, clay, or bentonite, synthetic layered silicates like magadiite or kenyaite, or mixtures of these materials. The layered silicate may be calcined or uncalcined, for example, to dry the material and remove water of crystallization. In some embodiments, the inorganic matrix material may also include an inorganic binder, such as cement, lime, gypsum, or suitable mixtures thereof, to bind the layered silicate. In some embodiments, the inorganic matrix material may also include other inorganic additives disclosed herein, such as fire-retardant additives, opacifiers, or combinations thereof. U.S. Patent Nos. 6,143,400; 6,083,619 discloses aerogel compositions including exemplary processes and inorganic matrix materials (incorporated herein by reference in their entirety). In some embodiments, the aerogel composition may include aerogel particles coated on or absorbed therein of woven materials, nonwoven materials, needle-punched nonwoven materials, wadding, netting, mats, felt, and combinations thereof. The composition may include an adhesive. It may also include additives as disclosed herein, such as flame-retardant additives, light-blocking agents, or combinations thereof. Example processes and aerogel compositions coated on or absorbed therein are disclosed in U.S. Patent Publication No. 2019 / 0264381A1 (which is incorporated herein by reference in its entirety).

[0145] As described herein, aerogel composites can be laminated or coated with other materials, such as a coating material reinforcement layer. In one embodiment, this disclosure provides a multilayer laminated material comprising: at least one base layer including a reinforcing aerogel composition, and at least one coating layer. In one embodiment, the coating layer comprises a reinforcing material. In one embodiment, the reinforcing aerogel composition is reinforced with a fiber reinforcement layer or an open-cell foam reinforcement layer. In one embodiment, this disclosure provides a multilayer laminated material comprising: a base layer including a reinforcing aerogel composition, and at least two coating layers including reinforcing materials, the two coating layers being located on opposite surfaces of the base layer. For example, this multilayer aerogel laminated composite can be manufactured according to the method and materials described in U.S. Patent No. 2007 / 0173157.

[0146] The overlay may include materials to help provide specific properties to the final composite structure, such as increased flexibility or reduced dust. The overlay material may be rigid or flexible. The overlay material may include a conductive layer or a reflective foil. For example, the overlay material may include a metallic or metallized material. The overlay material may include a nonwoven material. The overlay may be disposed on the surface of the composite structure or the reinforcing aerogel composite (e.g., a thermal control) forming the composite structure. The overlay may form a continuous coating or pouch around the composite structure or the reinforcing aerogel composite (e.g., a thermal control) forming the composite structure. In some embodiments, the one or more overlays may encapsulate the composite structure or the reinforcing aerogel composite forming the composite structure.

[0147] In one embodiment, the covering layer comprises a polymer sheet surrounding the composite structure; more specifically, the polymer material includes: polyester, polyethylene, polyurethane, polypropylene, polyacrylonitrile, polyamide, aramid; more specifically, polymers such as polyethylene terephthalate, low-density polyethylene, ethylene-propylene copolymer, poly(4-methylpentane), polytetrafluoroethylene, poly(1-butene), polystyrene, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polyvinyl fluoride, polyethylene acrylonitrile, polymethyl methacrylate, polyoxymethylene, polyphenylene sulfone, cellulose triacetate, polycarbonate, polyvinyl naphthalate, polycaprolactam, polyhexamethylene diamide, polyundecylamide, polyimide, or combinations thereof. In one embodiment, the polymer sheet comprises or is substantially composed of a foamed polymer material; more specifically, it comprises foamed polymer materials such as PTFE (ePTFE), foamed polypropylene (ePP), foamed polyethylene (ePE), foamed polystyrene (ePS), or combinations thereof. In a preferred embodiment, the covering material is substantially composed of a foamed polymer material. In one embodiment, the polymer sheet comprises or is substantially composed of a microporous polymer material characterized by pore sizes ranging from 0.1 μm to 210 μm, 0.1 μm to 115 μm, 0.1 μm to 15 μm, or 0.1 μm to 0.6 μm.

[0148] In one embodiment, the overlay material comprises or is substantially composed of a fluoropolymer material. In the context of this disclosure, the terms "fluoropolymer" or "fluoropolymer material" refer to a material primarily composed of a polyfluorocarbon compound. Suitable fluoropolymer overlay materials include, but are not limited to: polytetrafluoroethylene (PTFE), including microporous PTFE as described in U.S. Patent No. 5,814,405, and expanded PTFE (ePTFE), such as Gore-Tex® (available from WLGore); polyvinylidene fluoride (PVF); polyvinylidene fluoride (PVDF); perfluoroalkoxy (PFA); fluorinated ethylene-propylene (FEP); polychlorotrifluoroethylene (PCTFE); ethylene tetrafluoroethylene (ETFE); polyvinylidene fluoride (PVDF); ethylene trifluorochloroethylene (ECTFE); and combinations thereof. In a preferred embodiment, the overlay material is substantially composed of a fluoropolymer material. In a preferred embodiment, the overlay material is substantially composed of expanded PTFE (ePTFE) material.

[0149] In one embodiment, the overlay material comprises or is substantially composed of a fluoropolymer-free material. In the context of this disclosure, the terms "fluoropolymer-free" or "fluoropolymer-free material" refer to a material that does not contain fluoropolymers. Suitable fluoropolymer-free overlay materials include, but are not limited to: aluminized Mylar; low-density polyethylene, such as Tyvek® (available from DuPont); rubber or rubber composites; nonwoven materials, elastic fibers such as spadex, nylon, Lycra, or elastane; and combinations thereof. In one embodiment, the overlay material is a flexible overlay material.

[0150] In some embodiments, the overlay material may include automotive resins and polymers, such as resins and polymers with a maximum operating temperature of up to about 100°C, about 120°C, or about 150°C. For example, the overlay material may include acrylonitrile butadiene styrene (ABS), polycarbonate ABS, polypropylene, polyurethane, polystyrene, polyethylene, polycarbonate, polyimide, polyamide, PVC, or combinations thereof. For example, the aerogel composite and thermal control according to embodiments disclosed herein may include layers of automotive resin or automotive polymer, metallic or metallized layers, and an aerogel layer.

[0151] An adhesive can be used to attach the overlay to a substrate, the adhesive being suitable for fixing inorganic or organic overlay materials to a substrate reinforcement. Examples of adhesives that can be used in this disclosure include, but are not limited to: cement-based adhesives, sodium silicate, latex, pressure-sensitive adhesives, silicone, polystyrene, aerosol adhesives, urethane, acrylate adhesives, hot-melt bonding systems, bonding systems sold by 3M, epoxy resins, rubber resin adhesives, and polyurethane adhesive mixtures, such as those described in U.S. Patent No. 4,532,316.

[0152] The overlay can also be attached to the substrate using non-adhesive materials or techniques suitable for fixing inorganic or organic overlay materials to the substrate reinforcement. Examples of non-adhesive materials or techniques that can be used in this disclosure include, but are not limited to: heat sealing, ultrasonic stitching, RF sealing, stitching or threading, needle punching, sealing bags, rivets or buttons, clips, wrapping, or other non-adhesive press-fit materials.

[0153] The topcoat can be attached to the base layer at any stage of the manufacturing process of the aerogel composite. In one embodiment, the topcoat is attached to the base layer after the sol-gel solution is injected into the base reinforcement material but before gelation. In another embodiment, the topcoat is attached to the base layer after the sol-gel solution is injected into the base reinforcement material and subsequently gelled, but before aging or drying the gel material. In yet another embodiment, the topcoat is attached to the base layer after aging and drying the gel material. In a preferred embodiment, the topcoat is attached to the reinforcement material of the base layer before the sol-gel solution is injected into the base reinforcement material. The topcoat can be impermeable to both solids and fluids. The topcoat can be porous and permeable to fluids. In a preferred embodiment, the topcoat is porous and permeable to fluids and contains pores or holes of a sufficiently large diameter to allow fluid diffusion through the topcoat material. In another preferred embodiment, a topcoat layer is attached to the base reinforcement material before the sol-gel solution is injected, and the topcoat layer is porous and fluid-permeable, containing pores or holes of a sufficiently large diameter to allow fluid to diffuse through the topcoat material. In yet another preferred embodiment, a topcoat layer is attached to an open-cell foam reinforcement material before the sol-gel solution is injected, and the topcoat layer is porous and fluid-permeable, containing pores or holes of a sufficiently large diameter to allow fluid to diffuse through the topcoat material.

[0154] sunblock Aerogel compositions may include light-shielding agents to reduce the radiative component of heat transfer. At any point prior to gel formation, a light-shielding compound or a precursor thereof may be dispersed in a mixture comprising the gel precursor. Examples of light-shielding compounds include, but are not limited to, boron carbide (B4C), diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium dioxide, ferrotitanium, alumina, zirconium silicate, zirconium oxide, iron oxide (I), iron oxide (III), manganese dioxide, ferrotitanium (ilmenite), chromium oxide, carbides (e.g., SiC, TiC, or WC), or mixtures thereof. Examples of light-shielding compound precursors include, but are not limited to, TiOSO4 or TiOCl2. In some embodiments, the light-shielding compound used as an additive may exclude silicon carbide whiskers or fibers. When the aerogel composition is intended for use in electrical devices, such as as a barrier layer in batteries or other related applications, compositions including light-shielding agents may be desired to have high dielectric strength and high volumetric and surface resistivity. In such embodiments, the carbon additive used as a light-blocking agent may be non-conductive or modified to reduce conductivity. For example, the light-blocking agent may be surface-oxidized to reduce conductivity. In some embodiments, the carbon-containing additive with inherent conductivity is a light-blocking agent that can be used in an aerogel composition (intended for use in an electrical device). In such embodiments, the conductive carbon-containing additive may be used at concentrations below the permeation threshold to provide suitable dielectric strength for the composition, thereby enabling its use in an electrical device.

[0155] Fire-retardant additives The aerogel composition may include one or more fire-retardant additives. In the context of this disclosure, the term "fire-retardant additive" refers to a material that has an endothermic effect in the context of a fire reaction and can be incorporated into the aerogel composition. Furthermore, in certain embodiments, the endothermic decomposition (ED) onset temperature of the fire-retardant additive is no more than 100°C higher than the thermal decomposition onset temperature (Td) of the aerogel composition containing the fire-retardant additive, and in certain embodiments, the endothermic decomposition is no more than 50°C lower than the thermal decomposition onset temperature (Td) of the aerogel composition containing the fire-retardant additive. In other words, the endothermic decomposition of the fire-retardant additive has (T... d -50℃ to (T d The range of +100℃: Before, during, or even after incorporation into or mixing with a sol (e.g., silica sol prepared from alkyl silicates or water glass in various ways as understood in the art), the fire-retardant additive may be mixed with or otherwise dispersed in a medium including ethanol and optionally up to 10% vol water. The mixture may be mixed and / or stirred as needed to achieve substantially uniform dispersion of the additive in the medium. Not limited to theory, the use of the aforementioned clays and other fire-retardant additives in hydrated form provides additional endothermic effects. For example, xuyongite clay (available from Applied Minerals under the trade name DRAGONITE, or from Imerys under the trade name Halloysite) and kaolinite clay are aluminosilicate clays whose hydrated form has an endothermic effect (gas dilution) by releasing hydrated water at high temperatures. As another example, hydrated carbonates can release carbon dioxide upon heating or at high temperatures.

[0156] In the context of this disclosure, the term "heat of dehydration" refers to the amount of heat required for a material in its self-hydrated form to evaporate water (and dihydroxylate, if applicable) without exposure to high temperatures. Heat of dehydration is typically expressed on a per-unit-weight basis.

[0157] In certain embodiments, the fire-retardant additive of this disclosure has a thermal decomposition onset temperature of about 100°C or higher, about 130°C or higher, about 200°C or higher, about 230°C or higher, about 240°C or higher, about 330°C or higher, 350°C or higher, about 400°C or higher, about 415°C or higher, about 425°C or higher, about 450°C or higher, about 500°C or higher, about 550°C or higher, about 600°C or higher, about 650°C or higher, about 700°C or higher, about 750°C or higher, about 800°C or higher, or within any two of these values. In certain embodiments, the fire-retardant additive of this disclosure has a thermal decomposition onset temperature of about 440°C or 570°C. In a particular embodiment, the fire-retardant additive of this disclosure has a thermal decomposition initiation temperature that is higher or lower than that of the aerogel composition (without the fire-retardant additive) containing the fire-retardant additive, not exceeding 50°C, not exceeding 40°C, not exceeding 30°C, not exceeding 20°C, not exceeding 10°C, not exceeding 5°C, or within any two of these values.

[0158] The fire-retardant additives disclosed herein include clay materials, such as, but not limited to, layered silicate clays (e.g., illite), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), metamorphic kaolin, xuyongite (aluminum silicate; Al2Si2O5(OH)4), andeite (aluminum silicate; Al2Si2O5(OH)4), mica (silica mineral), diaspore (aluminum hydroxide; α-AlO(OH)), gibbsite (aluminum hydroxide), boehmite (aluminum hydroxide; γ-AlO(OH)), montmorillonite, aluminum bentonite, pyrophyllite (aluminum silicate; Al2Si4O) 10 (OH)2), monzoite, bleaching mica, bentonite, vermiculite, palygorskite, chlorite, magnesia bentonite, green opal, chrome bentonite, diaspore, metamorphic sculptile, chloroflavonite, halloysite, chrome aluminum quartz, kaolinite, terrazzo and orthorhombic quartz, sodium bicarbonate (NaHCO3), magnesium hydroxide (or magnesium dihydroxyl, "MDH"), aluminum oxide trihydrate ("ATH"), gypsum (calcium sulfate dihydrate; CaSO4‧2H2O), magnesia hydrate (MgCO3‧2H2O), magnesia hydrate (MgCO3‧3H2O), magnesia pentahydrate (MgCO3‧5H2O), magnesite (hydrated magnesium carbonate; Mg5(CO3)4(OH)2‧4H2O), and other carbonates such as, but not limited to, dolomite and lithium carbonate. In these clay materials, specific embodiments of this disclosure use clay materials having at least a partially layered structure. In certain embodiments of this disclosure, the clay material used as a fire-retardant additive in the aerogel composition has at least some water (e.g., in a hydrated form). This additive may be in a hydrated crystalline form or may be hydrated during the manufacture / processing of the compositions disclosed herein. In certain embodiments, the fire-retardant additive also includes low-melting-point additives that absorb heat without altering the chemical composition. Examples of such additives are low-melting-point glasses, such as inert glass microspheres. Other additives that may be used in the compositions disclosed include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2). In certain embodiments, other additives may include infrared shielding agents, such as, but not limited to, titanium dioxide or silicon carbide; vitrifying agents, such as, but not limited to, low-melting-point glass powder and calcium silicate; or charring agents, such as, but not limited to, phosphates and sulfates. In certain embodiments, the additive may require special processes, such as techniques to ensure uniform distribution of the additive without significant agglomeration that could alter product performance. Such process techniques may include additional static and dynamic mixers, stabilizers, adjustments to process conditions, and other techniques known in the art.

[0159] Amount of additives The amount of additives in the aerogel compositions disclosed herein can depend on the desired properties of the composition. The amount of additives used during the preparation and processing of the sol-gel composition is typically referred to as a weight percentage relative to the silica content of the sol. The amount of additives in the sol can vary in weight percentage from about 5 wt% to about 70 wt% relative to the silica content. In a particular embodiment, the amount of additives in the sol is between 10 wt% and 60 wt% relative to the silica content, and in a particular preferred embodiment, it is between 20 wt% and 40 wt% relative to the silica content. In exemplary embodiments, the amount of additives in the sol is in the range of about 5% to about 20%, about 10% to about 20%, about 10% to about 30%, about 10% to about 20%, about 30 wt% to about 50 wt%, about 35 wt% to about 45 wt%, or about 35 wt% to about 40 wt% relative to the silica content. In some embodiments, the amount of additive in the sol is at least about 10 wt% of the silica content, or about 10 wt% of the silica content. In some embodiments, the amount of additive ranges from about 5 wt% to about 15 wt% of the silica content. In certain embodiments, the additive may be of more than one type. One or more fire-retardant additives may also be present in the final aerogel composition. In some preferred embodiments including aluminosilicate fire-retardant additives, the additive is present in the aerogel composition at about 60-70 wt% of the silica content. For example, in some preferred embodiments including aluminosilicate fire-retardant additives such as kaolin or a combination of aluminosilicate fire-retardant additives such as kaolin and alumina trihydrate (“ATH”), the total amount of additive present in the aerogel composition is about 30-40 wt% of the silica content. As another example, in some preferred embodiments where the additive includes silicon carbide, the total amount of additive present in the aerogel composition is about 30-40 wt% of the silica content, for example, 35 wt%. For example, in some preferred embodiments where the additives include silicon carbide, the total amount of the additives present in the aerogel composition is about 5-15 wt% relative to the silicon dioxide content, for example 10 wt%.

[0160] When referring to the final reinforced aerogel composition, the amount of additive is typically referred to as a weight percentage of the final reinforced aerogel composition. The amount of additive in the final reinforced aerogel composition can vary within the range of about 1% to about 50%, about 1% to about 25%, or about 10% to about 25% of the reinforced aerogel composition by weight. In an exemplary embodiment, the amount of additive in the final reinforced aerogel composition is in the range of about 10% to about 20% of the reinforced aerogel composition by weight. In an exemplary embodiment, the amount of additive in the final reinforced aerogel composition (as a weight percentage of the composition) is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or within any of the above percentage ranges. In a particular embodiment, the amount of additive in the final reinforced aerogel composition is about 15% by weight of the reinforced aerogel composition. In certain embodiments, the amount of additive in the final reinforcing aerogel composition is about 13% by weight of the reinforcing aerogel composition. For example, in some preferred embodiments including additives such as silicon carbide, the total amount of additive present in the aerogel composition is about 10-20%, for example, about 15% by weight of the reinforcing aerogel composition. As another example, in some preferred embodiments where the additive includes silicon carbide, the total amount of additive present in the aerogel composition is about 3-5%, for example, about 4% by weight of the reinforcing aerogel composition.

[0161] The thermal decomposition initiation temperature of fire-retardant additives In certain embodiments, fire-retardant additives may be classified or grouped based on their thermal decomposition initiation temperature. For example, fire-retardant additives may be classified or grouped as additives having a thermal decomposition initiation temperature below about 200°C, below about 400°C, or above about 400°C. For example, additives having a thermal decomposition initiation temperature below about 200°C include sodium bicarbonate (NaHCO3), magnesia trihydrate (MgCO3·3H2O), and gypsum (calcium sulfate dihydrate; CaSO4·2H2O). As another example, additives having a thermal decomposition initiation temperature below about 400°C include alumina trihydrate (“ATH”), magnesite (hydrated magnesium carbonate; Mg5(CO3)4(OH)2·4H2O), and magnesium hydroxide (or magnesium dihydroxyl, “MDH”). For example, additives with a thermal decomposition initiation temperature below about 400°C include pyrite (aluminum silicate; Al2Si2O5(OH)4), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), boehmite (aluminum hydroxide; γ-AlO(OH)), or high-temperature phase change material (PCM).

[0162] In certain embodiments of this disclosure, the clay material (e.g., aluminosilicate clay, such as zeolite or kaolinite) used as an additive in the aerogel composition is in a dehydrated form, such as metazeolite or metakaolinite. Other additives that can be used in the compositions of this disclosure include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2). In certain embodiments, other additives may include infrared shading agents, such as, but not limited to, titanium dioxide or silicon carbide; vitrifying agents, such as, but not limited to, low-melting-point glass powder or calcium silicate; or charring agents, such as, but not limited to, phosphates and sulfates. In certain embodiments, the additives may require special processes, such as techniques to ensure that the additive is uniformly distributed without severe agglomeration that could alter product performance. Such process techniques may include additional static and dynamic mixers, stabilizers, adjustments to process conditions, and other techniques known in the art. One or more fire-retardant additives may also be present in the final aerogel composition.

[0163] In certain embodiments, the inclusion of additives (e.g., aluminosilicate clay-based materials, such as zeolite or kaolin) in the aerogel materials and compositions of this disclosure can provide improved high-temperature shrinkage properties. An example test method for high-temperature shrinkage is the "Standard Test Method for Linear Shrinkage of Preformed High-Temperature Thermal Insulation Subjected to Soaking Heat" (ASTM C356, ASTM International, West Conshohocken, PA). In this type of test (referred to as "heat soaking"), the material is exposed to temperatures above 1000°C for up to 60 minutes. In certain exemplary embodiments, the aerogel materials or compositions of this disclosure may have high-temperature shrinkage of about 20% or less, about 15% or less, about 10% or less, about 6% or less, about 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or within any two of these values; that is, any combination of linear shrinkage, width shrinkage, thickness shrinkage, or dimensional shrinkage.

[0164] In some exemplary embodiments, a specific base catalyst used to catalyze the precursor reaction can generate trace amounts of alkali metals in the aerogel composition. Trace amounts (e.g., 100 to 500 ppm) of base (e.g., sodium or potassium) in the aerogel material can have detrimental effects on high-temperature shrinkage and thermal durability. However, not limited to any particular mechanism or theory, aluminosilicate clay-based materials (e.g., metamorphic stone or kaolin) can isolate unstable bases, such as sodium or potassium, thereby reducing or eliminating the effects of bases on shrinkage and thermal durability. In specific embodiments of this disclosure, the aluminosilicate clay material is in a dehydrated form, such as metamorphic stone or metamorphic kaolin. For example, a significant reduction in thermal shrinkage and thermal durability can be achieved when the aerogel material or composition contains more than about 0.5 wt% metamorphic kaolin or metamorphic stone relative to silica. In exemplary embodiments, the amount of metamorphic kaolin or metamorphic stone that may be included in the aerogel material or composition ranges from about 0.5 wt% to about 3.0 wt% relative to the silica content.

[0165] Encapsulation layer or encapsulating material layer In some embodiments, the core portion of the multilayer material disclosed herein, or the multilayer material itself, may be encapsulated by an encapsulation layer. For example, the encapsulation layer may include one or more material layers surrounding the multilayer material and / or a material coating surrounding the multilayer material and / or the core portion of the multilayer material. For example, the encapsulation layer may include a film, layer, membrane, or coating. The encapsulation may be made of any material suitable for enclosing the composite structure or forming a reinforcing aerogel composite of the composite structure. For example, the encapsulation may reduce or eliminate the generation of dust or particulate material detached from the composite structure. The encapsulation material layer may be selected from polymers, elastomers, or combinations thereof. Examples of suitable polymers include polyethylene terephthalate (PET), polyethylene (PE), polyimide (PI), rubber, and nylon, which have extremely low thermal conductivity (less than 1 W / m), thereby having the effect of reducing the thermal conductivity of the entire system across the plane. In one embodiment, the encapsulation layer includes a polyethylene terephthalate layer.

[0166] The encapsulation layer may include at least one vent allowing air to flow in and out of the panel. The encapsulation may include at least one filter to filter particulate matter. In one exemplary embodiment, the encapsulation layer includes: a vent allowing air to flow in and out of the panel; and a particulate filter located above the vent, which retains particulate matter within the encapsulation. In another embodiment, the encapsulation layer includes an edge seal including at least one vent and at least one particulate filter. In yet another embodiment, the encapsulation layer includes an edge seal including at least one vent and at least one particulate filter, wherein the vent in the edge seal allows air to flow in and out of the edge of the encapsulation, and the filter captures and retains particulate matter in the flowing air to prevent air outside the encapsulation layer from being contaminated by particulate matter.

[0167] Thermal Capacity Layer In exemplary embodiments, the multilayer material may include a material or material layer providing heat capacity (i.e., a heat-capacity material), such as a material having a specific heat capacity of at least about 0.2 J / (gC). In some embodiments, the heat-capacity material has a specific heat capacity of at least about 0.5 J / (gC). For example, the heat-capacity material may include metals such as aluminum, titanium, nickel, steel, iron, or combinations thereof. In some embodiments, the multilayer material may include a layer or coating of the heat-capacity material. In some embodiments, the multilayer material may include particles of the heat-capacity material disposed within layers of the multilayer material, for example, disposed within layers of the aerogel composition. In a particular embodiment, the multilayer material may include at least one material layer providing heat capacity disposed adjacent to the aerogel composition. In a particular embodiment, the multilayer material may include at least one material layer providing heat capacity disposed between at least two of the multilayers of the aerogel composition. In exemplary embodiments, the multilayer material may include a material that combines thermal conductivity and heat capacity.

[0168] For example, the multilayer material may include materials that provide both heat capacity and thermal conductivity, such as metals like aluminum, titanium, nickel, steel, iron, or combinations thereof. As another example, the multilayer material may include one or more different materials or material layers that respectively provide heat capacity, thermal conductivity, or combinations thereof; for example, one layer may include a metal and another layer may include a conductive polymer. Preferably, the thermally conductive layer has a melting temperature of at least 300°C, preferably at least 600°C, more preferably at least 1000°C, and even more preferably at least 1500°C.

[0169] In some implementations, the heat-capacity material may be a self-phase change material. It is understood that for a phase change material to be suitable for widespread use in energy storage systems, the material should not only have a high heat capacity during the phase change but also be low-cost and self-constrained, i.e., requiring no sealing or special constraints within the device's operating temperature range, such as encapsulating battery modules. Additional desired properties for energy storage applications include high thermal conductivity for rapidly removing heat from heat-generating components and the ability to customize the temperature at which the phase change occurs.

[0170] In some implementations, the heat-capacity material has a thermal conductivity of at least about 200 mW / mK along its in-plane dimension.

[0171] Thermally Conductive Layer It has been found that the thermally conductive layer disclosed in this paper exhibits significantly enhanced heat dissipation capabilities across the entire xy-plane of the multilayer material, further improving durability under high thermal loads. Examples of high thermal conductivity materials include carbon fiber, graphite, silicon carbide, metals (including but not limited to copper, stainless steel, aluminum, etc.), and combinations thereof.

[0172] In an exemplary embodiment, the multilayer material may include a thermally conductive material or a layer of material that provides thermal conductivity. The thermally conductive layer of this disclosure helps to displace localized heat loads within a battery module or battery pack. For example, the thermally conductive layer may have an in-plane thermal conductivity of at least about 200 mW / mK. The thermally conductive material may include at least one layer comprising a metal, carbon, a conductive polymer, or a combination thereof.

[0173] In some embodiments of the foregoing aspects, the multilayer material may include one or more thermally conductive layers, i.e., having a thermal conductivity greater than 50 W / mK, preferably greater than 100 W / mK, and more preferably greater than 200 W / mK (all measured at 25°C). For example, the multilayer material may include at least one layer composed of or comprising a thermally conductive material, such as a layer comprising a metal, carbon, a conductive polymer, or a combination thereof. In the context of these embodiments, a thermally conductive material is defined as a material whose thermal conductivity is greater than that of an insulating material (e.g., an aerogel composition). In a particular embodiment, the thermally conductive material has a thermal conductivity at least about one level greater than that of the aerogel composition. In some embodiments, the multilayer material may include multiple layers of the aerogel composition. In a particular embodiment, the multilayer material may include at least one thermally conductive material layer disposed adjacent to the aerogel composition. In a particular embodiment, the multilayer material may include at least one thermally conductive material layer disposed between at least two of the multiple layers of the aerogel composition. In some embodiments, the multilayer material may include particles of the thermally conductive material disposed within the layers of the multilayer material, for example, within the layers of the aerogel composition.

[0174] To aid in heat dissipation and removal, in at least one embodiment, the thermally conductive layer is coupled to a heat sink. It should be understood that various types and configurations of heat sinks exist, as well as different techniques for coupling the heat sink and the thermally conductive layer, and this disclosure is not limited to the use of any single heat sink / coupling technique. For example, at least one thermally conductive layer of the multilayer material disclosed herein may be in thermal communication with an element of the cooling system of a battery module or battery pack (e.g., a cooling plate or cooling channel of the cooling system). As another example, at least one thermally conductive layer of the multilayer material disclosed herein may be in thermal communication with other elements of the battery pack, battery module, or battery system that can act as a heat sink (e.g., the walls of the battery pack, module, or system), or with other elements of the multilayer material disposed between battery cells. The thermal communication between the thermally conductive layer of the multilayer material and the heat sink element within the battery system allows excess heat to be transferred from one or more adjacent cells of the multilayer material to the heat sink, thereby reducing the impact, severity, or propagation of thermal events that may generate excess heat (e.g., as detailed herein).

[0175] Preferably, the thermally conductive layer has a melting temperature of at least 300°C, preferably at least 600°C, more preferably at least 1000°C, and even more preferably at least 1500°C.

[0176] The thickness of the thermally conductive layer can depend on the composition, the properties of other components of the multilayer material (e.g., compression pads), the number of thermally conductive layers included in the multilayer material, and various compositional factors. Functionally, the thermally conductive layer should be thick enough to provide the required in-plane thermal conductivity.

[0177] In some embodiments, the thermally conductive material (e.g., pyrolytic graphite sheet (PGS)) may have a thickness of about 0.010 mm, 0.025 mm, 0.05 mm, 0.07 mm, 0.10 mm, or within any two of these values, and an in-plane thermal conductivity in the range of about 600 to about 1950 W / mK. In some embodiments, the thermally conductive material (e.g., a metal sheet) may have a thickness of about 0.05 mm, about 0.07 mm, about 0.10 mm, about 0.20 mm, about 0.25 mm, about 0.30 mm, about 0.5 mm, about 0.75 mm, about 1 mm, about 1.5 mm, about 2 mm, about 3 mm, about 4 mm, about 5 mm, or within any two of these values.

[0178] In some implementations, the thermally conductive material may be a self-phase change material.

[0179] In some embodiments, thermal paste may be used between the layers of the multilayer material to ensure uniform heat conduction between such layers. Thermal paste as used herein refers to various materials, also known as thermal compounds, thermal greases, thermal interface materials (TIMs), thermal gels, thermal adhesives, heat dissipation compounds, and heat dissipation greases. For example, a thermal paste layer may be provided between the aerogel composition and any other layer, such as one or more layers comprising thermally conductive or heat-capacitant materials, one or more overlay layers, or encapsulation layers.

[0180] Sacrificial material layer In exemplary embodiments, the multilayer material may include a sacrificial material or a sacrificial material layer. In the context of this disclosure, the terms "sacrificial material" or "sacrificial layer" refer to a material or layer intended to be sacrificed or at least partially removed in response to mechanical, thermal, chemical, and / or electromagnetic conditions experienced by that layer. For example, the sacrificial material or sacrificial layer may decompose when exposed to high temperatures (e.g., high temperatures occurring before or during a battery thermal runaway event). In some embodiments, the sacrificial material layer may be disposed on an outer surface (e.g., the outer surface of the core portion of the multilayer material) or an external surface (e.g., the outer surface of the multilayer material).

[0181] In exemplary embodiments, the sacrificial material or layer of this disclosure may include a compressible pad having a compressive modulus of about 1 MPa, about 2 MPa, about 3 MPa, about 4 MPa, about 5 MPa, about 6 MPa, about 7 MPa, about 8 MPa, about 9 MPa, about 10 MPa, about 11 MPa, about 12 MPa, or within any two of these values. The sacrificial material layer may be selected from the group consisting of siloxanes, polyolefins, polyurethanes, phenolic resins, melamine, cellulose acetate, and polystyrene. In some cases, the material layer is in the form of a foam. In some embodiments, the compressible pad or foam may wear down due to exposure to mechanical (e.g., periodic) loads. In some embodiments, the compressible pad or foam decomposes after exposure to individual mechanical, chemical, and / or thermal events.

[0182] In some implementations, the chemical decomposition initiation temperature of the sacrificial material layer is in the range of about 200°C to about 400°C.

[0183] Suitable foams used as compressible pads in the embodiments disclosed herein have a density of less than about 1.0 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.20 g / cc or less, about 0.16 g / cc, about 0.10 g / cc or less, about 0.08 g / cc or less, or within any two of these values, and / or, based on the total volume of the foam, have a void volume content of at least about 20% to about 99%, specifically greater than or equal to about 30%. In one exemplary embodiment, the foam has a density of about 0.08 g / cc to about 0.50 g / cc, a 25% compressive force deflection (CFD) at about 27 kPa to about 55 kPa, and a compressive force deflection of less than about 10%, specifically less than 5%, at about 70°C, measured in accordance with ASTM D1056 by calculating the force (in kPa) required to compress the sample to 25% of its original thickness.

[0184] The polymer used for this foam can be selected from a wide variety of thermoplastic resins, thermoplastic resin mixtures, or thermosetting resins. Examples of thermoplastic resins that can be used include polyacetal, polyacrylic acid, styrene-acrylonitrile, polyolefin, acrylonitrile-butadiene-styrene, polycarbonate, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polyamide (e.g., but not limited to Nylon 6; Nylon 6,6; Nylon 6,10; Nylon 6,12; Nylon 11 or Nylon 12), polyamide-imide, polyarylate, polyurethane, ethylene propylene rubber (EPR), polyarylsulfone, polyethersulfone, polyphenylene sulfide, polyvinyl chloride, polysulfone, polyetheramide, polytetrafluoroethylene, fluorinated ethylene propylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyetherketone, polyetheretherketone, polyetherketoneketone, etc., or combinations including at least one of the above thermoplastic resins.

[0185] Examples of thermoplastic resin blends that can be used in this polymer foam include acrylonitrile-butadiene-styrene / nylon, polycarbonate / acrylonitrile-butadiene-styrene, acrylonitrile-butadiene-styrene / polyvinyl chloride, polyphenylene ether / polystyrene, polyphenylene ether / nylon, polysulfone / acrylonitrile-butadiene-styrene, polycarbonate / thermoplastic polyurethane, polycarbonate / polyethylene terephthalate, polycarbonate / polybutylene terephthalate, thermoplastic elastomer alloy, polyethylene terephthalate / polybutylene terephthalate, styrene-maleic anhydride / acrylonitrile-butadiene-styrene, polyetheretherketone / polyethersulfone, styrene-butadiene rubber, polyethylene / nylon, polyethylene / polyacetal, ethylene propylene rubber (EPR), etc., or combinations including at least one of the above blends.

[0186] Examples of thermosetting polymeric resins that can be used in this polymeric foam include polyurethane, epoxy resin, phenolic resin, polyester, polyamide, silicone, etc., or combinations thereof including at least one of the above thermosetting resins. Mixtures of thermosetting resins and mixtures of thermoplastic resins and thermosetting resins can be used.

[0187] Multilayer materials As described above, the multilayer material according to embodiments of this disclosure provides good compressibility, compressive elasticity, and compliance properties. When used as a thermal insulation between cells within a battery module, the thermally insulating sheet formed using the aerogel composition provides resistance to compressive deformation to accommodate cell expansion due to degradation and expansion of the active material during the battery's charge / discharge cycles. During the initial assembly of the battery module, a low load of 1 MPa or less is typically applied to the thermal insulation (e.g., the multilayer material disclosed herein). During use, for example, when cells within the battery module expand or swell during charge / discharge cycles, loads up to about 5 MPa may be applied to the multilayer material disclosed herein.

[0188] In one exemplary aspect, this disclosure provides a multilayer material that exhibits less than about 25% compressibility at about 25 kPa. Optionally, upon release of compression, the multilayer material may possess sufficient elasticity to recover to at least about 80%, 75%, 65%, 60%, or 50% of its original thickness. In some embodiments, the multilayer material exhibits less than about 25% compressibility in the range of about 25 kPa to about 35 kPa, and preferably less than about 50% compressibility at about 50 kPa. In some embodiments, the multilayer material exhibits compressibility in the range of about 25% to about 50% at about 50 kPa. In an exemplary embodiment, the multilayer material exhibits less than about 80% compressibility at about 245 kPa, for example, less than about 70% at about 235 kPa. In an exemplary embodiment, the multilayer material exhibits less than about 70% compressibility at about 345 kPa. When the multilayer material is compressed, the thermal conductivity of the multilayer material, including the reinforcing aerogel composition, preferably remains less than about 25 mW / m*K.

[0189] As described herein, the multilayer material may include multiple material layers, such as an insulating layer, a thermally conductive layer, a heat-capacitance layer, an encapsulating material layer, an abrasion-resistant layer, a fire-retardant / flame-retardant layer, a heat-reflective layer, a compressible layer (e.g., a compressible pad), a sacrificial layer, or a combination thereof. The combination and configuration of the layers in the multilayer material can be selected to obtain a desired combination of properties, such as compressibility, elasticity, thermal properties, fire reactivity, and other properties. In some embodiments, the multilayer material includes at least one compressible pad disposed between at least two layers of the reinforcing aerogel composition. For example, the compressible pad may be a foam or other compressible material, such as polyolefin, polyurethane, phenolic resin, melamine, cellulose acetate, or polystyrene. In certain embodiments, the multilayer material may also include at least one thermally conductive or heat-capacitance layer and at least one layer of the multilayer of the reinforcing aerogel composition. The thermally conductive or heat-capacitance material may absorb and / or disperse heat within the multilayer material. In some embodiments, the multilayer material may further include a heat-reflective layer. For example, the heat-reflective layer may include a metal foil or sheet.

[0190] In embodiments where the multilayer material comprises several layers, these layers can be attached to other layers, for example, by an adhesive mechanism selected from the group consisting of aerosol adhesives, urethane-based adhesives, acrylate adhesives, hot melt adhesives, epoxy resins, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, these layers can be attached by non-adhesive mechanisms (e.g., mechanisms selected from the group consisting of flame bonding, needle punching, sewing, sealing bags, rivets, buttons, clips, wrapping, supports, and combinations thereof). In some embodiments, any combination of the above-described adhesive and non-adhesive mechanisms can be used to attach these layers together.

[0191] The final product of multilayer materials The multilayer material according to embodiments of this disclosure can be formed into various end products. In the simplest configuration, the multilayer material can be in the form of a sheet. The sheet can be formed continuously or semi-continuously, for example, as a rolled product, or can be cut from a larger sheet or otherwise formed into a sheet having the desired size and shape. The sheet material can be used to form a thermal barrier between battery cells. In other configurations, the reinforced aerogel composition can be formed into a pouch, for example, to house a pouch cell for a battery, or formed into a cylinder to house a cylindrical battery cell.

[0192] The multilayer material disclosed herein can be formed into a range of three-dimensional shapes, including panels, pipe preforms, half-shell preforms, elbows, joints, bags, cylinders, and other shapes frequently required for the application of insulating materials in industrial and commercial applications.

[0193] Unless otherwise expressly provided, the singular forms “a” and “the” as used in this specification and the appended claims include multiple meanings. Unless the context clearly provides otherwise, the term “or” as used in this specification and the appended claims generally includes “and / or” in its meaning.

[0194] As used herein, “about” means approximately or close to, and in the context of describing a numerical value or range, it means ±5% of the numerical value. In one implementation, the term “about” may include conventional rounding based on the significant figures of the numerical value. Furthermore, the phrase “about 'x' to 'y'” includes “about 'x' to about 'y'”.

[0195] The terms “composition” and “complex” used in this document are used interchangeably.

[0196] The terms “compressible pad” and “compressible layer” used in this article are used interchangeably.

[0197] In the context of this disclosure, the terms "aerogel," "aerogel material," or "aerogel matrix" refer to a gel comprising a framework of interconnected structures, a corresponding network of interconnected pores integrated within the framework, and containing a gas (e.g., air) as a dispersion interstitial medium, and characterized by physical and structural properties (based on nitrogen porosity testing) attributable to the aerogel: (a) an average pore size in the range of about 2 nm to about 100 nm, (b) a porosity of at least 80% or more, and (c) a surface area of ​​about 100 m². 2 / g or more.

[0198] Therefore, the aerogel materials disclosed herein include any aerogel or other open-cell materials that satisfy the defining elements described in the preceding paragraph; including materials that can be otherwise classified as dry gels, cryogels, dual gels, microporous materials, etc.

[0199] Aerogel materials can be further characterized by other physical properties, including: (d) a pore volume of about 2.0 mL / g or more, specifically about 3.0 mL / g or more; (e) a density of about 0.50 g / cc or less, specifically about 0.3 g / cc or less, more specifically about 0.25 g / cc or less; and (f) at least 50% of the total pore volume comprising pores having a pore size between 2 and 50 nm (although embodiments disclosed herein include aerogel frameworks and compositions comprising pores having a pore size greater than 50 nm, as discussed in more detail below). However, characterizing a compound as an aerogel material does not require these additional properties to be met.

[0200] In the context of this disclosure, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of a composite. Examples of aerogel compositions include, but are not limited to, fiber-reinforced aerogel composites; aerogel composites including additive elements (e.g., opacifiers); aerogel composites reinforced by an open-pore macroporous framework; aerogel-polymer composites; and composite materials that incorporate aerogel microparticles, particles, granules, microbeads, or powders into solid or semi-solid materials, such as by binding agents, resins, cements, foams, polymers, or similar solid materials. Aerogel compositions are typically obtained after removing the solvent from the various gel materials disclosed herein. The resulting aerogel compositions may then undergo further processing or treatment. The various gel materials may also undergo additional processing or treatment known or available in the art prior to solvent removal (or liquid extraction or drying).

[0201] The aerogel compositions disclosed herein may include reinforced aerogel compositions. In the context of this disclosure, the term "reinforced aerogel composition" refers to an aerogel composition that includes a reinforcing phase in an aerogel material, where the reinforcing phase is not part of the aerogel framework itself.

[0202] In the context of this disclosure, the term "fiber-reinforced aerogel composition" refers to a reinforced aerogel composition comprising a fiber-reinforced material as a reinforcing phase. Examples of fiber-reinforced materials include, but are not limited to, discrete fibers, woven materials, dry-laid nonwoven materials, wet-laid nonwoven materials, needle-punched nonwoven materials, cotton wadding, nets, mats, felts, and / or combinations thereof.

[0203] Fiber reinforcing materials can be selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof. Fiber reinforcing materials may include a range of materials, including but not limited to: polyesters, polyolefin terephthalates, polyethylene naphthalate, polycarbonates (e.g., Rayon, Nylon), cotton (e.g., Lycra manufactured by DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), oxidized PAN, uncarbonized heat-treated PAN (e.g., manufactured by SGL carbon), glass or glass fiber-based materials (e.g., S-glass, 901 glass, 902 glass, 475 glass, E-glass), silica-based fibers such as quartz (e.g., Quartz manufactured by Saint-Gobain), Q-felt (manufactured by Johns Hopkins University), etc. Manville-manufactured fibers, Saffil (manufactured by Saffil), Durablanket (manufactured by Unifrax), and other silica fibers; Duraback (manufactured by Carborundum); polyaramid fibers such as Kevlar, Nomex, and Sontera (all manufactured by DuPont); Conex (manufactured by Taijin); polyolefins such as Tyvek (manufactured by DuPont), Dyneema (manufactured by DSM), and Spectra (manufactured by Honeywell); other polypropylene fibers such as Typar and Xavan (both manufactured by DuPont); fluoropolymers such as PTFE (trade name Teflon) (manufactured by DuPont) and Goretex (manufactured by WLGORE); and silicon carbide fibers such as Nicalon (manufactured by COI). Ceramics, ceramic fibers such as Nextel (manufactured by 3M), acrylic polymers, wool, silk, hemp, leather, suede fibers, PBO-Zylon fibers (manufactured by Tyobo), liquid crystal materials such as Vectan (manufactured by Hoechst), Cambrelle fibers (manufactured by DuPont), polyurethane, polyamide, wood fibers, boron, aluminum, iron, stainless steel fibers, and other thermoplastic materials such as PEEK, PES, PEI, PEK, PPS. This glass or glass fiber-based fiber reinforcement can be manufactured using one or more technologies. In certain embodiments, it is desirable to manufacture them using carding and cross-laying or air-laid processes. In exemplary embodiments, carded and cross-laid glass or glass fiber-based fiber reinforcements offer specific advantages over air-laid materials. For example, carded and cross-laid glass or glass fiber-based fiber reinforcements can provide a consistent material thickness for a given basis weight of reinforcement. In certain additional embodiments, it is desirable to further needle-punch the fiber reinforcement, interlacing the fibers along the z-direction to enhance the mechanical and other properties of the final aerogel composition.

[0204] In the context of this disclosure, "thermal runaway" generally refers to a sudden and rapid increase in cell temperature and pressure due to various operating factors, which can correspondingly cause excessively high temperatures to propagate throughout the associated module. Potential causes of thermal runaway in such systems may include, for example, cell defects and / or short circuits (internal and external), overcharging, cell puncture or rupture (e.g., in the event of an accident), and excessively high ambient temperatures (e.g., typically above 55°C). During normal use, cells generate heat due to internal resistance. Under normal power / current loads and ambient operating conditions, the temperature within most lithium-ion batteries can be easily controlled within the range of 20°C to 55°C. However, stress conditions (e.g., high power consumption at high cell / ambient temperatures, and defects in individual cells) can dramatically increase localized heat generation. In particular, above critical temperatures, exothermic chemical reactions within the cell are activated. Moreover, chemical heat generation typically increases exponentially with temperature. Therefore, heat generation becomes far greater than available heat dissipation. Thermal runaway can lead to cell venting and internal temperatures exceeding 200°C.

[0205] In the context of this disclosure, the term "foam" refers to a material comprising a framework of interconnected polymer structures having a substantially homogeneous composition, a corresponding network or aggregate of pores integrated within the framework, and formed by dispersing a proportionate amount of gas in the form of bubbles in a liquid or resin foam material such that, upon curing of the foam material into a solid structure, the bubbles are retained as pores. Generally, foams can be manufactured using a wide variety of processes—see, for example, U.S. Patent Nos. 6,147,134; 5,889,071; 6,187,831; and 5,229,429. Therefore, the foam materials of this disclosure include any material satisfying the defining elements described in this paragraph, including compounds that can be otherwise classified as OCMF materials, macroporous materials, etc. Foams as defined in this disclosure can be of the types of thermoplastic materials, elastomers, and thermosetting materials (duromers).

[0206] In the context of this disclosure, the terms "flexible" and "flexible" refer to the ability of a material or composition to bend or flex without macroscopic structural failure. The insulation of this disclosure is capable of bending at least 5°, at least 25°, at least 45°, at least 65°, or at least 85° without macroscopic failure; and / or having a bending radius less than 4 feet, less than 2 feet, less than 1 foot, less than 6 inches, less than 3 inches, less than 2 inches, less than 1 inch, or less than U inches without macroscopic failure. Similarly, the terms "highly flexible" or "highly flexible" refer to a material capable of bending to at least 90° and / or having a bending radius less than U inches without macroscopic failure. Furthermore, the terms "classified as flexible" and "categorized as flexible" refer to materials or compositions that can be classified as flexible according to ASTM C101 (ASTM International, West Conshohocken, PA).

[0207] The insulating layer of this disclosure may be flexible, highly flexible, and / or classified as flexible. The aerogel composition of this disclosure may also be draped. In the context of this disclosure, the terms "draped" and "drapeability" refer to the ability of a material to be bent or flexed to 90° or greater without macroscopic failure, given a radius of curvature of about 4 inches or less. The insulating layer according to a particular embodiment of this disclosure is flexible so that the composition is non-rigid and can be applied to and conform to a three-dimensional surface or object, or pre-formed into various shapes and configurations to simplify installation or application.

[0208] In the context of this disclosure, the terms "additive" or "additive element" refer to materials that may be added to the aerogel composition before, during, or after the manufacture of the aerogel. Additives may be added to modify or improve desired properties in the aerogel, or to counteract undesirable properties in the aerogel. Typically, additives are added to the aerogel material before gelation to a precursor liquid, during gelation to a transitional material, or after gelation to a solid or semi-solid material.

[0209] Examples of additives include, but are not limited to, microfibers, fillers, reinforcing agents, stabilizers, thickeners, elastic compounds, opacifiers, pigmentation compounds, radiation-absorbing compounds, radiation-reflecting compounds, fire-retardant additives, corrosion inhibitors, thermally conductive components, components providing heat capacity, phase change materials, pH adjusters, redox adjusters, HCN mitigators, exhaust gas mitigators, conductive compounds, dielectric compounds, magnetic compounds, radar-blocking components, hardeners, anti-shrinkage agents, and other aerogel additives known to those skilled in the art. In some embodiments, the component providing heat capacity may include a material having a specific heat capacity of at least about 0.3 J / (gC). In some embodiments, the material providing heat capacity has a specific heat capacity of at least about 0.5 J / (gC). For example, the material providing heat capacity may include metals such as aluminum, titanium, nickel, steel, iron, or combinations thereof. In some embodiments, the multilayer material may include one or more layers or coatings of the material providing heat capacity. In some embodiments, the multilayer material may include particles of the material that provide heat capacity, disposed within one or more insulating layers comprising an aerogel composition.

[0210] In certain embodiments, the aerogel compositions, reinforced aerogel compositions, and multilayer materials disclosed herein can function during high-temperature events, for example, providing thermal protection during high-temperature events as disclosed herein. High-temperature events are caused by temperatures of at least about 1 cm... 2 At least approximately 25 kW / m² over an area lasting at least 2 seconds 2 At least approximately 30 kW / m 2 At least approximately 35 kW / m 2 Or at least about 40 kW / m 2 Characterized by heat flux. Approximately 40 kW / m² 2 The heat flux is correlated with the heat flux caused by a typical fire (Behavior of Charring Solids under Fire-Level Heat Fluxes; Milosavljevic, I., Suuberg, EM; NISTIR 5499; September 1994). In special cases, this high-temperature event is at least about 10 cm. 2 A heat flux of approximately 40 kW / m² is applied to the area for at least one minute.

[0211] In the context of this disclosure, the terms "thermal conductivity" and "TC" refer to a measure of the ability of a material or composition to transfer heat between two surfaces on either side of the material or composition, where a temperature difference exists between the two surfaces. Thermal conductivity is specifically measured as the amount of heat transferred per unit time and per unit surface area divided by the temperature difference. It is typically recorded in the International System of Units (SI) as mW / m*K (milliwatts per meter) Kelvin. The thermal conductivity of a material can be determined by test methods known in the art, including but not limited to: Test Method for Steady-State Thermal Transmission Properties by Means of the Heat Flow Meter Apparatus (ASTM C518, ASTM International, West Conshohocken, PA); a Test Method for Steady-State Heat Flux Measurements and Thermal Transmission Properties by Means of the Guarded-Hot-Plate Apparatus (ASTM C177, ASTM International, West Conshohocken, PA); a Test Method for Steady-State Heat Transfer Properties of Pipe Insulation (ASTM C335, ASTM International, West Conshohocken, PA); a Thin Heater Thermal Conductivity Test (ASTM C1114, ASTM International, West Conshohocken, PA); and Standard Test Method for Thermal Transmission Properties of Thermally Conductive Electrical Insulation Materials (ASTM D5470, ASTM International, West Conshohocken, PA).Determination of thermal resistance by means of guarded hot plate and heatflow meter methods (EN 12667, British Standards Institution, United Kingdom); or Determination of steady-state thermal resistance and related properties - Guarded hot plate apparatus (ISO 8203, International Organization for Standardization, Switzerland). Because different methods may lead to different results, it should be understood that, in the context of this disclosure, unless otherwise explicitly stated, thermal conductivity measurements are obtained according to ASTM C518 (Test Method for Steady-State Thermal Transmission Properties by Means of the Heat Flow Meter Apparatus) at ambient atmospheric pressure, at a temperature of approximately 37.5°C, and under a compressive load of approximately 2 psi. Measurements reported according to ASTM C518 are typically closely related to any measurements taken according to EN 12667 with any relevant adjustments to that compressive load.

[0212] Thermal conductivity measurements can also be obtained under compression, at atmospheric pressure, and at a temperature of about 10°C. Thermal conductivity measurements at 10°C are typically 0.5-0.7 mW / mK lower than the corresponding thermal conductivity measurements at 37.5°C. In certain embodiments, the insulating layer of this disclosure has a thermal conductivity at 10°C of about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or within any two of these values.

[0213] In the context of this disclosure, the term "density" refers to a measure of the mass of a material or composition per unit volume. The term "density" generally refers to the apparent density of a material, and the bulk density of a composition. Density is typically recorded as kg / m³. 3Or g / cc. The density of a material or composition (e.g., aerogel) can be determined by methods known in the art, including but not limited to Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, PA); Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTM C167, ASTM International, West Conshohocken, PA); Determination of the apparent density of preformed pipe insulation (EN 13470, British Standards Institution, United Kingdom); or Determination of the apparent density of preformed pipe insulation (ISO 18098, International Organization for Standardization, Switzerland). Because different methods can lead to different results, it should be understood that, in the context of this disclosure, unless otherwise explicitly stated, density measurements are obtained under ASTM C167 (Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations) at 2 psi compression for thickness measurement.In certain embodiments, the aerogel material or composition of this disclosure has a density of about 1.0 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.25 g / cc or less, about 0.20 g / cc or less, about 0.18 g / cc or less, about 0.16 g / cc or less, about 0.14 g / cc or less, about 0.12 g / cc or less, about 0.10 g / cc or less, about 0.05 g / cc or less, about 0.01 g / cc or less, or within any two of these values.

[0214] The hydrophobicity of an aerogel material or composition can be expressed as water vapor absorption. In the context of this disclosure, the term "water vapor absorption" refers to a measure of the potential of an aerogel material or composition to absorb water vapor. Water vapor absorption can be expressed as the percentage (by weight) of water absorbed or otherwise retained by the aerogel material or composition when exposed to water vapor under specific measurement conditions. The water vapor absorption of an aerogel material or composition can be determined by methods known in the art, including but not limited to Standard Test Method for Determining the Water Vapor Sorption of Unfaced Mineral Fiber Insulation (ASTM C1104, ASTM International, WestConshohocken, PA); Thermal insulating products for building applications: Determination of long-term water absorption by diffusion (EN 12088, British Standards Institution, United Kingdom). Because different methods can lead to different results, it should be understood that, in the context of this disclosure, unless otherwise expressly stated, water vapor absorption measurements are obtained under ambient pressure for 24 hours (modified from 96 hours according to ASTM C1104) at 49°C and 95% humidity, according to ASTM C1104 (Standard Test Method for Determining the Water Vapor Sorption of Unfaced Mineral Fiber Insulation). In certain embodiments, the aerogel material or composition of this disclosure may have water vapor absorption of about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or within any two of these values. Compared to another aerogel material or composition, an aerogel material or composition with improved water vapor absorption will have a lower water vapor absorption / retention percentage relative to the reference aerogel material or composition.

[0215] The hydrophobicity of an aerogel material or composition can be represented by measuring the equilibrium contact angle of a water droplet at its interface with the surface of the material. The aerogel materials or compositions of this disclosure may have a water contact angle of about 90° or greater, about 120° or greater, about 130° or greater, about 140° or greater, about 150° or greater, about 160° or greater, about 170° or greater, about 175° or greater, or within any two of these values.

[0216] In the context of this disclosure, the terms "heat of combustion," "HOC," and "ΔHC" are measures of the heat released during the combustion or exothermic decomposition of a material or composition. Heat of combustion is typically recorded as caloric heat released per gram of aerogel material or composition (cal / g), or as megajoules of heat released per kilogram of material or composition (MJ / kg). The heat of combustion of a material or composition can be determined by methods known in the art, including but not limited to Reaction to firetests for products—Determination of the gross heat of combustion (calorific value) (EN ISO 1716, International Organization for Standardization, Switzerland; EN adopted). In the context of this disclosure, unless otherwise stated, heat of combustion measurements are obtained according to the EN ISO 1716 standard (Reaction to fire tests for products—Determination of the gross heat of combustion (calorific value)).

[0217] In the context of this disclosure, all thermal analyses and related definitions refer to measurements performed in air at ambient pressure, starting at 25°C and increasing to 1000°C at a rate of 20°C per minute. Therefore, any changes to these parameters (or re-performing the measurements under these conditions) must be taken into account when measuring and calculating the thermal decomposition onset point, peak heat release temperature, peak heat absorption temperature, etc.

[0218] In the context of this disclosure, the terms "thermal decomposition initiation point" and "TD" refer to a measure of the lowest temperature at which a rapid exothermic reaction occurs within a material or composition due to the decomposition of organic materials. Thermogravimetric analysis (TGA) can be used to measure the thermal decomposition initiation point of organic materials within a material or composition. The TGA curve of a material describes the weight loss (mass percentage) of the material as it is exposed to increasing ambient temperature, thus representing thermal decomposition. The thermal decomposition initiation point of a material can be correlated with the intersection of the following tangents to the TGA curve: the line tangent to the baseline of the TGA curve, and the line tangent to the TGA curve at the point of maximum slope during a rapid exothermic decomposition event associated with the decomposition of organic materials. In the context of this disclosure, unless otherwise stated, the TGA analysis provided in this paragraph is used to obtain measurements of the thermal decomposition initiation point of organic materials.

[0219] The thermal decomposition onset point of a material can also be measured using differential scanning calorimetry (DSC). The DSC curve of a material describes the heat (mW / mg) released by the material as it is exposed to a gradually increasing ambient temperature. The thermal decomposition onset point of a material can be correlated with the point in the DSC curve where the increase in ΔmW / mg (change in heat output) is greatest, thus indicating the exothermic generation of the aerogel material. In the context of this disclosure, unless otherwise explicitly stated, measurements of the thermal decomposition onset point using DSC, TGA, or both are obtained using a heating rate of 20 °C / min, further defined in the preceding paragraph. DSC and TGA provide similar values ​​for this thermal decomposition onset point, and tests are often run simultaneously, thus results can be obtained from both.

[0220] In the context of this disclosure, the terms "endothermic decomposition initiation point" and "TED" refer to a measure of the lowest temperature at which an endothermic reaction occurs within a material or composition due to decomposition or dehydration. The endothermic decomposition initiation point of a material or composition can be measured using thermogravimetric analysis (TGA). A TGA curve of a material describes the weight loss (mass percentage) of the material as it is exposed to increasing ambient temperature. The thermal decomposition initiation point of a material can be correlated with the intersection of the following tangents to the TGA curve: the line tangent to the baseline of the TGA curve, and the line tangent to the TGA curve at the point of maximum slope during rapid thermal decomposition or dehydration of the material. In the context of this disclosure, unless otherwise stated, measurements of the endothermic decomposition initiation point of a material or composition are obtained using the TGA analysis provided in this paragraph.

[0221] In the context of this disclosure, the terms "furnace temperature rise" and "ΔTR" refer to a measure of the difference between the maximum temperature (TMAX) of a material or composition under thermal decomposition conditions and its baseline temperature (typically the final temperature or TFIN) under thermal decomposition conditions. Furnace temperature rise is typically recorded in degrees Celsius or °C. The furnace temperature rise of a material or composition can be determined by methods known in the art, including but not limited to Reaction to fire tests for building and transport products: Non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). In the context of this disclosure, unless otherwise stated, furnace temperature rise measurements are obtained according to conditions equivalent to EN ISO 1182 (Reaction to fire tests for building and transport products: Non-combustibility test). In certain embodiments, the aerogel compositions of this disclosure may have a furnace temperature rise of about 100°C or less, about 90°C or less, about 80°C or less, about 70°C or less, about 60°C or less, about 50°C or less, about 45°C or less, about 40°C or less, about 38°C or less, about 36°C or less, about 34°C or less, about 32°C or less, about 30°C or less, about 28°C or less, about 26°C or less, about 24°C or less, or within any two of these values. In the context of compositional stability at high temperatures, for example, a lower furnace temperature rise of the first composition compared to the second composition would be considered an improvement of the first composition relative to the second composition. It is contemplated herein that the furnace temperature rise of the compositions is reduced when one or more flammable additives are added, compared to compositions without any flammable additives.

[0222] In the context of this disclosure, the terms "burning time" and "TFLAME" refer to a measure of the sustained combustion of a material or composition under thermal decomposition conditions, and "sustained combustion" means that combustion on any visible portion of a sample lasts for 5 seconds or longer. Burning times are typically recorded in seconds or minutes. The burning time of a material or composition can be determined by methods known in the art, including but not limited to Reaction to fire tests for building and transport products: Non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). In the context of this disclosure, unless otherwise stated, burning time measurements are obtained according to conditions equivalent to EN ISO 1182 (Reaction to fire tests for building and transport products: Non-combustibility test). In a particular embodiment, the aerogel composition of this disclosure has a burning time of about 30 seconds or less, about 25 seconds or less, about 20 seconds or less, about 15 seconds or less, about 10 seconds or less, about 5 seconds or less, about 2 seconds or less, or within any two of these values. In the context of this document, for example, a burning time of a first composition that is shorter than that of a second composition will be considered an improvement of the first composition relative to the second composition. It is anticipated here that the burning time of a composition is reduced when one or more fire-retardant additives are added, compared to a composition that does not contain any fire-retardant additives.

[0223] In the context of this disclosure, the terms "mass loss" and "ΔM" refer to a measure of the amount of material, composition, or compound lost or burned under thermal decomposition conditions. Mass loss is typically recorded as a weight percentage or wt%. The mass loss of a material, composition, or compound can be determined by methods known in the art, including but not limited to: Reaction tofire tests for building and transport products: Non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). In the context of this disclosure, unless otherwise stated, mass loss measurements are obtained according to conditions equivalent to EN ISO 1182 (Reaction to fire tests for building and transport products: Non-combustibility test). In certain embodiments, the insulating layer or aerogel composition of this disclosure may have a mass loss of about 50% or less, about 40% or less, about 30% or less, about 28% or less, about 26% or less, about 24% or less, about 22% or less, about 20% or less, about 18% or less, about 16% or less, or within any two of these values. In the context herein, for example, a mass loss of the first composition that is lower than that of the second composition will be considered an improvement of the first composition relative to the second composition. It is contemplated herein that the mass loss of the composition is reduced when one or more fire-retardant additives are added, compared to a composition that does not contain any fire-retardant additives.

[0224] In the context of this disclosure, the term "peak heat release temperature" refers to a measure of the ambient temperature at which the exothermic release due to decomposition is at its maximum. The peak heat release temperature of a material or composition can be measured using TGA analysis, differential scanning calorimetry (DSC), or a combination thereof. DSC and TGA provide similar values ​​for the peak heat release temperature, and tests are often run simultaneously, thus providing results from both. In a typical DSC analysis, a heat flux versus temperature rise is plotted, and the peak heat release temperature is the temperature at which the highest peak appears on such a curve. In the context of this disclosure, unless otherwise stated, the TGA analysis described in this paragraph is used to obtain measurements of the peak heat release temperature of a material or composition.

[0225] In the context of endothermic materials, the term "peak heat absorption temperature" refers to a measure of the ambient temperature at which the endothermic absorption due to decomposition is at its minimum. The peak heat absorption temperature of a material or composition can be measured using TGA analysis, differential scanning calorimetry (DSC), or a combination thereof. In a typical DSC analysis, a heat flux versus temperature rise graph is plotted, and the peak heat absorption temperature is the temperature at which the lowest peak appears on such a curve. In the context of this disclosure, unless otherwise stated, the TGA analysis provided in this paragraph is used to obtain measurements of the peak heat absorption temperature of a material or composition.

[0226] In the context of this disclosure, the terms "low flammability" and "low flammability" refer to materials or compositions that satisfy the following combination of properties: i) furnace temperature rise of 50°C or less; ii) burning time of 20 seconds or less; and iii) mass loss of 50 wt% or less. In the context of this disclosure, the terms "non-flammable" and "non-flammable" refer to materials or compositions that satisfy the following combination of properties: i) furnace temperature rise of 40°C or less; ii) burning time of 2 seconds or less; and iii) mass loss of 30 wt% or less. It is anticipated that the flammability of the composition (e.g., the combination of furnace temperature rise, burning time, and mass loss) will be reduced upon including one or more flammable additives, as described herein.

[0227] In the context of this disclosure, the terms "low flammability" and "low combustibility" refer to a low-flammability material or composition having a total heat of combustion (HOC) of less than or equal to 3 MJ / kg. In the context of this disclosure, the terms "non-flammability" and "non-combustible" refer to a non-flammable material or composition having a heat of combustion (HOC) of less than or equal to 2 MJ / kg. It is anticipated that the HOC of the composition will decrease upon inclusion of one or more flammable additives, as described herein.

[0228] In the context of this disclosure, the term "hydrophobically bonded silicon" refers to silicon atoms within the framework of a gel or aerogel that include at least one hydrophobic group covalently bonded to the silicon atom. Examples of hydrophobically bonded silicon include, but are not limited to, silicon atoms in silica groups within the gel framework, formed from gel precursors including at least one hydrophobic group (e.g., MTES or DMDS). Hydrophobically bonded silicon may also include, but is not limited to, silicon atoms in the gel framework or on the surface of the gel, which are treated with a hydrophobic agent (e.g., HMDZ) to impart or improve hydrophobicity by incorporating additional hydrophobic groups into the composition. Hydrophobic groups in this disclosure include, but are not limited to, methyl groups, ethyl groups, propyl groups, isopropyl groups, butyl groups, isobutyl groups, tert-butyl groups, octyl groups, phenyl groups, or other alternative or non-alternative hydrophobic organic groups known to those skilled in the art. In the context of this disclosure, the terms "hydrophobic group," "hydrophobic organic material," and "hydrophobic organic content" specifically exclude readily hydrolyzable organosilicon-bonded alkoxy groups on the framework of the gel material, which are reaction products between organic solvents and silanol groups. NMR analysis can distinguish these excluded groups from their hydrophobic organic content. The amount of hydrophobically bound silicon contained in aerogels can be analyzed using NMR spectroscopy (e.g., CP / MAS 29Si solid-state NMR). NMR analysis of aerogels allows for the characterization and relative quantification of M-type hydrophobically bound silicon (monofunctional silica, such as TMS derivatives); D-type hydrophobically bound silicon (bifunctional silica, such as DMDS derivatives); T-type hydrophobically bound silicon (trifunctional silica, such as MTES derivatives); and Q-type silicon (tetrafunctional silica, such as TEOS derivatives). By allowing the classification of specific types of hydrophobically bound silicon into subtypes (e.g., classifying T-type hydrophobically bound silicon into T1, T2, and T3 samples), NMR analysis can also be used to analyze the bonding chemistry of hydrophobically bound silicon contained in aerogels. Specific details relating to NMR analysis of silica materials can be found in Geppi et al., “Applications of Solid-State NMR to the Study of Organic / Inorganic Multicomponent Materials”, pages 7-9 (Appl. Spec. Rev. (2008), 44-1: 1-89), which are incorporated herein by reference to the specific pages mentioned.

[0229] Characterization of hydrophobically bound silicon in CP / MAS 29Si NMR analysis can be based on the following chemical shift peaks: M1 (30 to 10 ppm); D1 (10 to -10 ppm), D2 (-10 to -20 ppm); T1 (-30 to -40 ppm), T2 (-40 to -50 ppm), T3 (-50 to -70 ppm); Q2 (-70 to -85 ppm), Q3 (-85 to -95 ppm), Q4 (-95 to -110 ppm). These chemical shift peaks are approximate and exemplary and are not intended to be limiting or restrictive. Precise chemical shift peaks attributable to various types of silicon within a material depend on the specific chemical composition of the material and can generally be interpreted by those skilled in the art through routine experiments and analysis.

[0230] In the context of this disclosure, the terms "hydrophobic organic content," "hydrophobic content," or simply "hydrophobic content" refer to the amount of hydrophobic organic material bonded to the framework in an aerogel material or composition. The hydrophobic organic content of an aerogel material or composition can be expressed as a weight percentage of the amount of hydrophobic organic material on the aerogel framework relative to the total amount of material in the aerogel material or composition. Those skilled in the art can calculate the hydrophobic organic content based on the properties and relative concentrations of the materials used to manufacture the aerogel material or composition. The hydrophobic organic content can also be measured by thermogravimetric analysis (TGA) of the host material, preferably in an oxygen environment (although TGA in other gas environments can also be used). Specifically, the percentage of hydrophobic organic material in the aerogel can be correlated with the percentage of weight loss of the hydrophobic aerogel material or composition during the TGA analysis at the heat of combustion temperature, adjusted for moisture loss, residual solvent loss, and loss of readily hydrolyzable alkoxy groups during the TGA analysis. Other alternative techniques, such as differential scanning calorimetry, elemental analysis (especially carbon), chromatography, nuclear magnetic resonance spectroscopy, and other analytical techniques known to those skilled in the art, can be used to measure and determine the hydrophobic content in the aerogel compositions of this disclosure. In certain cases, a combination of known techniques may be useful or necessary for determining the hydrophobic content of the aerogel compositions of this disclosure.

[0231] The aerogel material or composition of the present invention may have a hydrophobic organic content of 50 wt% or less, 40 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 8 wt% or less, 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, or any two of these values.

[0232] The term "fuel content" refers to the total amount of combustible material in an aerogel material or composition, which can be correlated with the percentage of weight loss of the aerogel material or composition during TGA or TG-DSC analysis at the heat of combustion temperature, and adjusted for moisture loss. The fuel content of an aerogel material or composition may include hydrophobic organic content, as well as other combustible residual alcohol solvents, fillers, reinforcing materials, and readily hydrolyzable alkoxy groups.

[0233] In the context of this disclosure, the term "ormosil" includes the aforementioned materials as well as other organically modified materials, sometimes referred to as "ormocer". Ormosil is commonly used as a coating, wherein an ormosil film is cast onto a matrix material via a sol-gel process or the like. Other examples of organic-inorganic hybrid aerogels disclosed herein include, but are not limited to, silica-polyether, silica-PMMA, silica-chitosan, carbides, nitrides, and other combinations of the aforementioned organic and inorganic aerogels that form compounds. Published U.S. Patent Publication No. 20050192367 (paragraphs

[0022] -

[0038] and

[0044] -

[0058] ) includes teachings on such hybrid organic-inorganic materials and is incorporated herein by reference in accordance with separately mentioned sections and paragraphs.

[0234] The use of multilayer materials in battery modules or battery packs Compared to conventional batteries, lithium-ion batteries (LIBs) are considered one of the most important energy storage technologies due to their high operating voltage, low memory effect, and high energy density. However, safety issues are a serious obstacle to the large-scale application of LIBs. Under abuse conditions, exothermic reactions can lead to the release of heat, which can trigger subsequent unsafe reactions. The situation worsens because the heat released by the abused cell can activate a series of reactions, leading to catastrophic thermal runaway.

[0235] With the continuous improvement of energy density in lithium-ion batteries, enhancing their safety has become increasingly urgent for the development of electrical devices such as electric vehicles. The mechanisms that trigger safety issues vary for different battery chemistry types. This technology focuses on tuning multilayer materials and their corresponding configurations to achieve favorable thermal and mechanical properties. The multilayer materials of this technology provide an effective heat dissipation strategy under both normal and thermal runaway conditions, while ensuring the stability of the LIB in normal operating modes (e.g., withstanding applied compressive stress).

[0236] The multilayer materials disclosed herein can be used to separate, insulate, and protect battery cells or battery assemblies having batteries of any configuration, such as pouch cells, cylindrical cells, prismatic cells, and groups and modules comprising or including any such cells. The multilayer materials disclosed herein can be used in rechargeable batteries (e.g., lithium-ion batteries), solid-state batteries, and any other energy storage devices or technologies requiring separation, insulation, and protection.

[0237] Passive devices, such as cooling systems, can be used in conjunction with the multilayer materials of this disclosure within the battery module or battery pack.

[0238] Multilayer materials according to various embodiments of the present disclosure are used in battery packs comprising modules of multiple single cell units or battery units to thermally separate the modules of said single cell units or battery units from each other.

Claims

1. A multilayer material for use as a thermal barrier in an energy storage system, said multilayer material comprising: The core component includes an insulating layer having a thermal conductivity of less than 50 mW / mK at 25°C and less than 60 mW / mK at 600°C, obtained according to ASTM C518 standard, along the thickness dimension of the insulating layer under a compressive load of 2 psi; and An outer portion, disposed outside the core portion, includes a thermally conductive layer having a thermal conductivity of at least 200 mW / mK, obtained according to ASTM C518 standard under a compressive load of 2 psi along the in-plane dimension of the thermally conductive layer. The thermally conductive layer is substantially L-shaped, such that the vertical portion of the L-shaped thermally conductive layer is separated from the insulating layer, and the horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer.

2. The multilayer material according to claim 1, wherein, The thermally conductive layer is in contact with the insulating layer.

3. The multilayer material according to claim 1 or 2, wherein, The thermally conductive layer comprises at least one layer consisting of a metal, carbon, a conductive polymer, or a combination thereof.

4. The multilayer material according to claim 1 or 2, wherein, The thermally conductive layer comprises a metal including aluminum, copper, or steel.

5. The multilayer material according to claim 1 or 2, wherein, The thermally conductive layer is the outer layer of the multilayer material.

6. The multilayer material according to claim 1 or 2, wherein, The thermally conductive layer is in the form of a group consisting of mesh, sheet, and foil.

7. The multilayer material according to claim 1 or 2, wherein, The insulating layer includes mica, ceramics, inorganic fiber cotton, resin, or inorganic foam.

8. The multilayer material according to claim 1 or 2, wherein, The insulating layer comprises aerogel.

9. The multilayer material according to claim 8, wherein, The aerogel includes reinforcing materials.

10. The multilayer material according to claim 9, wherein, The reinforcing material includes fibers selected from organic polymer-based fibers, inorganic fibers, carbon-based fibers, or combinations thereof.

11. The multilayer material according to claim 10, wherein, The fibers are in the form of discrete fibers, woven materials, needle-punched nonwoven materials, cotton wool, nets, pads, felts and / or combinations thereof.

12. The multilayer material according to claim 10 or 11, wherein, The inorganic fibers are selected from glass fibers, rock fibers, metal fibers, boron fibers, ceramic fibers, basalt fibers, or combinations thereof.

13. The multilayer material according to claim 8, wherein, The aerogel includes silica-based aerogel.

14. The multilayer material according to claim 8, wherein, The aerogel includes one or more additives, which are present at a level of at least 5 to 20 percent by weight of the aerogel.

15. The multilayer material according to claim 14, wherein, The one or more additives are present at a level of at least 10 to 20% by weight of the aerogel.

16. The multilayer material according to claim 14 or 15, wherein, One or more additives include fire-retardant additives.

17. The multilayer material according to claim 14 or 15, wherein, The one or more additives include light-blocking agents selected from B4C, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, TiC, WC, carbon black, titanium dioxide, ferrotitanium dioxide, zirconium silicate, zirconium oxide, iron oxide I, iron oxide III, manganese dioxide, ferrotitanium dioxide, chromium oxide, or mixtures thereof.

18. The multilayer material according to claim 14, wherein, The one or more additives include: a light-blocking agent comprising silicon carbide.

19. The multilayer material according to claim 14, wherein, The one or more additives include a combination of fire-retardant additives and light-blocking agents.

20. The multilayer material according to claim 8, wherein, The aerogel has a density in the range of 0.25 g / cc to 1.0 g / cc.

21. The multilayer material according to claim 8, wherein, The aerogel has a flexural modulus of 2 MPa to 8 MPa.

22. The multilayer material according to claim 8, wherein, The aerogel exhibits compressive resistance, wherein the compressive resistance at 25% strain is between 40 kPa and 180 kPa.

23. The multilayer material according to claim 1, further comprising a heat-capacity layer disposed between a portion of the thermally conductive layer and the insulating layer, wherein, The heat capacity layer has a specific heat capacity of at least 0.2 J / (gC).

24. The multilayer material according to claim 23, wherein, The heat capacity layer includes a phase change material.

25. The multilayer material according to claim 23, wherein, The heat-capacity layer includes metals such as aluminum, titanium, nickel, steel, or iron.

26. The multilayer material according to claim 1, further comprising a sacrificial material layer disposed between a portion of the thermally conductive layer and the insulating layer.

27. The multilayer material according to claim 26, wherein, The sacrificial material layer comprises materials selected from the group consisting of siloxanes, polyolefins, polyurethanes, phenolic resins, melamine, cellulose acetate, and polystyrene.

28. The multilayer material according to claim 26 or 27, wherein, The sacrificial material layer is in the form of foam.

29. The multilayer material according to claim 26 or 27, wherein, The chemical decomposition initiation temperature of the sacrificial material layer is in the range of 200°C to 400°C.

30. The multilayer material according to claim 1, further comprising an encapsulation layer disposed between the thermally conductive layer and the insulating layer.

31. The multilayer material according to claim 30, wherein, The encapsulation layer includes one or more polymer layers.

32. The multilayer material according to claim 1, wherein, The multilayer material has an average thickness between 2 mm and 10 mm in its uncompressed state.

33. The multilayer material according to claim 1, wherein, The thermally conductive layer is substantially L-shaped, such that the vertical portion of the L-shaped thermally conductive layer is separated from the insulating layer, and wherein the horizontal portion of the L-shaped thermally conductive layer is in contact with the insulating layer; and wherein one or more of an encapsulating material layer, a sacrificial material layer, and a heat capacity layer are disposed between the vertical portion of the L-shaped thermally conductive layer and the insulating layer.

34. The multilayer material according to claim 1, wherein, The multilayer material has a thermal resistivity of at least 0.02 K / W.

35. The use of the multilayer material according to claim 1 in a battery pack, wherein the battery pack includes a plurality of single cell units or modules of battery units for thermally separating the single cell units or modules of battery units from each other.

36. The use according to claim 35, wherein, A runaway event occurring in one or more battery cells or battery cell modules of a component of the battery pack will not cause damage to the battery cells or modules of the battery pack components separated from the battery pack component at the location of the runaway event by a multilayer material according to any one of claims 1 to 34.

37. A battery module, comprising: A first battery cell having a first surface; The second battery cell has a second surface, which is opposite to the first surface; The multilayer material according to any one of claims 1 to 34 is disposed between the first surface and the second surface; and The heat exchange system is in contact with the first battery cell, the second battery cell, and the thermally conductive layer of the multilayer material.

38. The battery module according to claim 37, wherein, The multilayer material according to any one of claims 1 to 32 covers at least 80% of the surface area of ​​the opposing first and second surfaces.

39. The battery module according to claim 37 or 38, wherein, The insulating layer of the multilayer material extends into the heat exchange system.

40. The battery module according to claim 37 or 38, wherein, The thermally conductive layer of the multilayer material is in thermal communication with the heat exchange system.

41. The battery module according to claim 37 or 38, wherein, The thermally conductive layer of the multilayer material is in thermal communication with the first battery cell and / or the second battery cell.

42. The battery module according to claim 41, wherein, The thermally conductive layer of the multilayer material is in contact with the first battery cell and / or the second battery cell.

43. The battery module according to claim 37 or 38, wherein, The battery module has a thermal resistance coefficient of at least 0.01, wherein the thermal resistance coefficient is the ratio of the thermal resistance of the multilayer material to the area energy density of the battery cells in the battery module, and wherein the area energy density of the battery module is the ratio of the total energy density of all cells in the battery module to the outer surface of the battery module.

44. The battery module according to claim 37 or 38, wherein, The multilayer material has a thickness coefficient of at least 0.3, wherein the thickness coefficient is the ratio of the thickness of the multilayer material to the area energy density of the battery cell.

45. A battery pack comprising a plurality of modules and one or more spacer layers disposed between adjacent modules, wherein, The one or more spacer layers comprise a multilayer material according to any one of claims 1 to 34.

46. ​​The battery pack according to claim 45, wherein, At least one of the plurality of modules is a battery module according to any one of claims 37 to 44.

47. An apparatus comprising a battery pack according to claim 45 or 46.

48. The apparatus according to claim 47, wherein, The device is a laptop computer, PDA, mobile phone, label scanner, audio device, video device, display panel, camera, digital camera, desktop computer, military portable computer, military telephone, laser rangefinder, digital communication device, intelligence gathering sensor, electronic integrated clothing, night vision equipment, power tool, calculator, radio, remote control device, GPS device, handheld and portable television, car starter, flashlight, acoustic device, portable heating device, portable vacuum cleaner, or portable medical tool.

49. A vehicle comprising a battery pack according to claim 45 or 46.

50. The vehicle according to claim 49, wherein, The vehicle in question is an electric vehicle.

51. A method for designing an energy storage system, comprising: Assemble one or more battery cells to form an array; Calculate the area energy density of the array, wherein the area energy density of the array is the ratio of the total energy density of all cells in the array to the outer surface of the array; The thermal resistance and compressibility thickness of the multilayer material according to claim 1 are selected based on the area energy density of the array, so that the energy storage system has a thermal resistance coefficient of at least 0.01 and a thickness coefficient of at least 0.3, wherein the thickness coefficient is the ratio of the thickness of the multilayer material to the area energy density of the array, and wherein the thermal resistance coefficient is the ratio of the thermal resistance of the multilayer material to the area energy density of the array; and The multilayer material is placed in and / or around the array.

52. The method according to claim 51, wherein, The selection of the thermal resistance and the compressibility thickness includes: Calculate the thermal resistance coefficient of the multilayer material; The minimum compressible thickness of the multilayer material is read from the thermal propagation map; and Select a compression thickness greater than the minimum compression thickness.

53. The method according to claim 51 or 52, wherein, The selection of the thermal resistance and the compressibility thickness includes: Calculate the thickness coefficient of each battery cell in the array; The minimum thermal resistance of the multilayer material is read from the thermal propagation diagram; and For the multilayer material, a thermal resistance greater than the minimum thermal resistance is selected.

54. The method according to claim 51 or 52, wherein, Setting the multilayer material includes: Separately form the multilayer material and the array, and The multilayer material is inserted next to the battery cells of the array.

55. The method according to claim 51 or 52, wherein, Placing the multilayer material includes forming the multilayer material directly in and / or in situ in the array.

56. The method according to claim 55, wherein, Placing the multilayer material includes coating, depositing, or filling the multilayer material in and / or around the array.

Citation Information

Patent Citations

  • Ormosil aerogels containing silicon bonded linear polymers

    US20050192367A1

  • Flexible coherent insulating structures

    US20070173157A1

  • Heat insulation composition for improving heat insulation and soundproofing functions, containing aerogel, and method for manufacturing heat insulation fabric by using same

    US20190264381A1

  • Improvement in ornamentation of glassware

    US220038A

  • Phase separating polyurethane prepolymers and elastomers prepared by reacting a polyol having a molecular weight of 600-3500 and isocyanate and a low molecular weight chain extender in which the ratios of reactants have a limited range

    US4532316A